Modelling a decade of daily open water evaporation for existing and planned water storages: A spatially explicit analysis for the Pilbara region of north-western Australia - David L. McJannet; Stephen B. Stewart; Dejun Cai; Thomas G. Van Niel; Tim R. McVicar; Steven D. Boxall (Journal of Hydrology, 2026)

Semi‐Natural Habitats Buffer the Effects of Crop Diversification on Arthropod Pest Control Services in Agricultural Landscapes - Thomas Perrot; Léa Beaumelle; Eva Thomine; Yann Tricault; Nicolas Desneux; Matthias Albrecht; Péter Batáry; Felix Bianchi; Klaus Birkhofer; Aliette Bosem Baillod; Rebecca Chaplin‐Kramer; Anne‐Marie Cortesero; et al. (Ecology Letters, 2026)
Crop diversification is a promising strategy to strengthen pest control services in agricultural landscapes. Diversifying crops may limit pests through host crop dilution or by enhancing top‐down control by their enemies. However, crop diversification may also benefit generalist pests through higher resource continuity. Using a large‐scale dataset encompassing 742 landscapes across 13 countries, we assessed the impact of landscape‐scale crop diversity on the abundance of natural enemies, the potential for biological control, and insect pest abundance. Crop diversification did not increase the overall abundance of natural enemies or the potential for biological pest control. Instead, crop diversity primarily favoured the abundance of specialist natural enemies and pests in highly simplified landscapes, an effect that was reduced in landscapes with high proportions of semi‐natural habitats. Lastly, low proportions of host crops in the landscape were associated with higher abundances of natural enemies. Taken together, our results indicate that crop diversification is not a ‘one size fits all’ strategy to control agricultural pests, and that other landscape characteristics, such as high amounts of semi‐natural habitats, must be considered to enhance biological pest control services.

Deep Dark Futures: Foresighting Human Impacts on Mesopelagic Ecosystem Services - Ben Scoulding; Alistair J. Hobday; Rowan Trebilco; Heidi Pethybridge; Ingrid van Putten; Katherine Baker; Karen Evans; David Green; Eriko Hoshino; Haris Kunnath; Clothilde Langlais; Tim P. Lynch; et al. (Fish and Fisheries, 2026)
Most of the global mesopelagic zone lies beyond the jurisdiction of any single government or entity, making equitable access and sustainable management for ecosystem services (ES) difficult. Here, a foresighting approach was used to examine the plausible consequences of four speculative scenarios of human activity on the mesopelagic zone and its associated ES. Large‐scale Harvest represented the provisioning ES, with concerns over unsustainable removal of mesopelagic biota. Climate Mitigation, a regulating ES, involved harvesting and then dumping mesopelagic biota to maximise carbon drawdown. In Geopolitical Manoeuvring, the scenario focused on cultural ES; mesopelagic fisheries were used as a geopolitical instrument to assert claims over ocean spaces. Finally, Mineral Extraction, a supporting ES, considered the impact of deep‐sea mining on mesopelagic ecosystems. Drivers and indicators for each scenario were identified, and qualitative network models were created to assess impact on the different system components using press perturbations. Model outputs highlighted the central role that mesopelagic biota play in supporting and regulating other ecosystem components and the likely negative impacts of reduced biomass on higher order predators and ocean carbon storage. Interestingly, biological indicators performed poorly as early warning signals of change across all scenarios; instead, the most effective indicators were related to science and technology, economics and governance. International agreements for sustainable use of the mesopelagic zone are needed to avoid loss of ES underpinning all scenarios. While this foresighting focused on the mesopelagic zone, the approach of developing scenarios, models and indicators has broader applicability to studies of other systems.

Biological Sex Is Binary and Rooted in Anisogamy - Tim Janicke; Göran Arnqvist; Pierre‐André Crochet; Patrice David; Philippe Jarne; Jussi Lehtonen; Thomas Lenormand; Edward H. Morrow; Geoff A. Parker; Paul A. Saunders; Jeanne Tonnabel; Frédéric Veyrunes; et al. (Ecology Letters, 2026)
The definition of biological sex has become a renewed focus of societal debate, fuelled by the conflation of biological principles with discussions of human gender diversity. Here, we argue that conceptual clarity critically depends on separating these domains. Drawing on evolutionary theory and empirical evidence, we maintain that biological sex is best defined as a binary classification of male and female reproductive strategies rooted in anisogamy, characterised by the production of two discrete gamete types of different sizes. We stress that gamete size constitutes the ultimate criterion for biological sex and that this definition applies consistently across sexual systems, from separate‐sexed species to hermaphrodites, irrespective of variation in karyotype, hormonal profile, somatic phenotype, or behaviour. Further, we emphasise that evolutionary insights offer a coherent explanation for recurring, though not universal, associations between biological sex and patterns of sex‐specific selection, sexual dimorphism and parental care. We conclude that the definition of biological sex as a binary classification based on gamete size is a powerful scientific framework compatible with the diversity of sexual phenotypes found in anisogamous organisms and distinct from the concept of human gender.

Groundwater-based water services as complex socio-hydrogeological systems: insights from Vietnam’s Mekong Delta - Naomi Carrard; Diana Gonzalez; Jess MacArthur; Nguyen Anh Minh; Nguyen Dinh Giang Nam; David Rodgers; Tim Foster (Hydrogeology Journal, 2026)
Groundwater systems are critical to global water security, yet the complex interactions between household coping strategies, resource sustainability, and climate change remain difficult to govern. This study applies qualitative systems mapping to characterise socio-hydrogeological dynamics in Vietnam’s Mekong Delta, a region currently facing intensifying saline intrusion and rapid land-use change. Drawing on a household survey ( n = 404) and in-depth interviews ( n = 25) in Sóc Trăng and Trà Vinh provinces, three critical system interactions were identified: (1) climate variability and household adaptation intensify groundwater system pressures, (2) policy-practice gaps undermine effective management of a multisource water system, and (3) social vulnerability and water stress constrain resilience. Together, these interactions illustrate how household behaviours, institutional arrangements, and resource conditions are interconnected in ways that shape system behaviour. These findings advance socio-hydrogeological frameworks by using systems mapping to make visible the relationships and interactions that influence groundwater-based water services. The research offers evidence for policymakers, suggesting that inclusive, climate-resilient service delivery depends on integrating actual household water behaviours into planning and groundwater governance, moving beyond a singular focus on piped supply.

Sexual selection in plants and animals: toward a unified framework - Jeanne Tonnabel; Patrice David; Tim Janicke (Trends in Ecology & Evolution, 2026)

Role of holocellulose on thermal annealing, loss of combustion reactivity and morphological changes in biomass pyrolysis - Erik Freisewinkel; Francesca Cerciello; Tim Eisenbach; David Tarlinski; Antonio Fabozzi; Martin Schiemann; Roland Span; Viktor Scherer; Osvalda Senneca (Fuel, 2026)

The Use of Digital Image Processing in the Modelling of a Roller Compaction Milling Operation - David Wilson; Alexa Mesham; Felix Tim Bölle (Pharmaceutical Research, 2026)

Plasma pTau181 is associated with subjective cognitive concerns but not objective cognitive decline or structural brain integrity measures in midlife - Ashleigh Barrett-Young; Erin E. Cawston; Brigid Ryan; Wickliffe C. Abraham; Antony Ambler; Tim Anderson; Kirsten Cheyne; Elizabeth Goodin; Sean Hogan; Renate M. Houts; David Ireland; Annchen R. Knodt; et al. (GeroScience, 2026)
Although plasma pTau181 has been shown to accurately discriminate patients with Alzheimer’s disease from healthy older adults, there are few studies of plasma biomarkers among middle-aged populations. Given the potential utility of plasma AD biomarkers such as pTau181 in screening for disease risk, examining pTau181 in a middle-aged cohort without AD is important for future implementation. The objectives of this study were to characterise plasma pTau181 in a middle-aged birth cohort aged 45 years and to investigate associations with early indicators of dementia risk. Participants were members of the Dunedin Multidisciplinary Health and Development Study, a longitudinal study of 1037 people born in New Zealand in 1972–1973. Plasma pTau181, self-reported cognitive concerns, MRI-based brain structure, and DunedinPACE (an epigenetic biomarker of biological ageing) were measured at age 45; cognition was measured in childhood and age 45. Plasma pTau181 concentrations at age 45 ( n = 854, 49% female) were associated with self-reported cognitive concerns (β = 0.09, p = .008); however, no significant associations were observed with objective cognitive decline, worse structural brain integrity, or biological ageing. Higher plasma pTau181 was associated with self-reported cognitive concerns at age 45, but not objective AD-related measures. The association of plasma pTau181 and self-reported cognitive concerns in this cohort suggests that AD pathology may begin to accumulate by age 45 and may be associated with subtle changes in cognition that are not at objectively measurable levels. Graphical Abstract

Seaweed-enriched formulated broodstock diet improves post-settlement survival of a commercial sea urchin - Rick Verkooijen; Symon Dworjanyn; Michael Salini; Minnie Harvey; David Francis; Fletcher Warren-Myers; Tim Dempster (Aquaculture, 2026)

Commercial scale test of purple sea urchin roe enhancement aquaculture - Xavier J. Smith; Tim Dempster; Michael Salini; David Francis; Fletcher Warren-Myers (Aquaculture, 2026)

In situ evaluation of an active-passive sampling (APS) technique for monitoring psychoactive compounds in effluent wastewater - Allen Jun Anies; Maria Laimou-Geraniou; Maarten Quireyns; Tim Boogaerts; Cara Byns; Taja Verovšek; David Heath; Ester Heath; Alexander L.N. van Nuijs; Adrian Covaci; Ronny Blust; Raewyn M. Town (Environmental Pollution, 2026)

Solar-thermal membrane distillation: Opportunities and challenges - Julianne Rolf; John Floyd; Tim Chomiak; Ze He; Ruikun Xin; Naomi Fuentes; Kuichang Zuo; Jingbo Wang; Omar Alrehaili; Rayan Alghanayem; Moustafa M. Abo El-Fadl; Mohamed A. El-Naggar; et al. (Desalination, 2026)

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Exploring the interplay of epigenetics and individualization - Denis Meuthen; Joseph I. Hoffman; Joachim Kurtz; Ane Liv Berthelsen; Nayden Chakarov; Rebecca S. Chen; Angelica Coculla; Jürgen R. Gadau; Toni I. Gossmann; Max Mühlenhaupt; Tania Chavarria-Pizarro; Tim M. Rapp; et al. (Trends in Ecology & Evolution, 2026)

Cell Painting reveals polypharmacological activity on the V-ATPase by the F-ATPase inhibitor Cyhexatin - Franziska A. Hecker; Maximilian Grohs; Tim Koenig; Karsten Niehaus; David Gnutt; Sven Geibel (Pesticide Biochemistry and Physiology, 2026)

Opportunities for remote sensing to monitor freshwater water quality after extreme weather events: A systematic review - Jiatan Liang; Andres Felipe Suárez-Castro; Tim Malthus; David P. Hamilton (Journal of Hydrology, 2026)

Large-scale estimation of carrying capacities in agricultural Crown lands of Manitoba, Canada using land cover datasets - Jan Bryan M. Encabo; Marcos R.C. Cordeiro; Emma J. McGeough; David Walker; Kim H. Ominski; Tim A. McAllister (Agricultural Systems, 2026)

Utilising Benford's Law in the Validation of Precipitation Datasets - Amee Gollop; Sarah Wilson Kemsley; Tim Osborn; Manoj Joshi; David Stevens; Ian Harris (International Journal of Climatology, 2026)
The increasing magnitude and complexity of precipitation datasets necessitate robust and efficient data integrity assessment. This study systematically applies Benford's Law, a mathematical theorem describing leading digit frequencies, as a novel diagnostic tool for precipitation data in the environmental and hydroclimate sciences. We present a reproducible and robust methodology, demonstrating that global monthly precipitation consistently conforms to Benford's Law across diverse data types, including raw observations, gridded products, reanalysis and synthetic simulations. This key finding fundamentally challenges traditional assumptions regarding the influence of data origin on Benford's Law adherence, significantly broadening its applicability. Our findings underscore the importance of underlying quantitative characteristics for successful application: while regional analyses reveal that monthly precipitation data in the United Kingdom and Ireland do not conform to Benford's Law‐based principles, a shift to daily temporal granularity successfully restores conformance, highlighting how temporal resolution can introduce the necessary data properties. This research uniquely positions Benford's Law as a powerful, complementary diagnostic tool capable of detecting subtle data corruptions, as demonstrated through an artificial experiment. Ultimately, this work advances the utility of Benford's Law in climate research, providing a scalable method to enhance the reliability of foundational datasets critical for climate modelling, forecasting and a wide array of hydroclimatological applications.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Skin sea surface temperature diagnostics in a regional ocean model - Jie Yu; David D. Flagg; Tommy G. Jensen; Tim J. Campbell; Qing Wang; Denny P. Alappattu (Ocean Modelling, 2026)

Transauricular Vagus Nerve Stimulation in Acute Ischaemic Stroke Requiring Mechanical Thrombectomy: Sham-Controlled, Randomised Device Trial - Gareth L. Ackland; David Crane; Sanjali Ahuja; Amour Patel; Tim Martin; Mareena Joseph; Onika Ottley; Rizwan Hameed; Priyanthi Dias; Salma Begum; Johannes Schroth; Russ Hewson; et al. (Translational Stroke Research, 2026)
Autonomic dysfunction leads to hemodynamic instability and immunosuppression after ischaemic stroke, and is independently associated with worse outcomes. We hypothesized that non-invasive peripheral neuromodulation, using transcutaneous auricular vagal nerve stimulation (tVNS), may reduce blood pressure variability and/or reverse immunosuppression early after ischaemic stroke requiring mechanical thrombectomy (MT). In this pre-registered phase 2 study (NCT05417009), we randomized 36 patients >18 years referred for emergent MT following an acute ischaemic stroke. Patients were randomized to receive bilateral auricular active-tVNS or sham-tVNS, for the entire MT and the morning after admission. Participants, clinicians and investigators were masked to treatment allocations. The primary outcome was systolic blood pressure variability (coefficient of variation) over the entire first 24h after mechanical thrombectomy, analysed by intention-to-treat. Secondary outcomes were whole blood RNA sequencing. Explanatory measures were time/frequency-domain measures of heart rate variability. Active-tVNS was safe in this hyperacute stroke setting, with no serious adverse events recorded. The systolic blood pressure coefficient of variability over the first 24h was 0.106±0.029 after active-tVNS, compared to 0.107±0.027 after sham-tVNS (p=0.93). Active-tVNS increased the relative expression of genes coordinating tumor-necrosis factor and toll-like receptor signaling, in parallel with alterations in heart rate variability over the first 24h after MT. This phase 2 study established thatearly tVNS is safe and feasible in the hyperacute phase of acute ischaemic stroke requiring MT, but did not alter systolic blood pressure variability. Trial registration number: NCT05417009, registered 8 TH June 2022.

The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Optimizing bioenergy biofuel harvest: a comparative analysis of stepwise and integrated methods for economic and environmental sustainability - Muhammad Umer Arshad; David Archer; Nictor Namoi; Daniel Wasonga; Chunhwa Jang; Tim Rooney; DoKyoung Lee (Bioresource Technology, 2026)

Chronic Fatty Acid Exposure Disrupts SH-SY5Y and Neuronal Differentiation and Is a Potential Link Between Type-2 Diabetes and Alzheimer’s Disease - Imogen L. Targett; Kate Pring; Ana I. Martinez Valiente; David Qualtrough; Myra E. Conway; Lucy A. Crompton; Tim J. Craig (Molecular Neurobiology, 2026)
Alzheimer’s disease (AD) is the most common cause of dementia, for which there is no curative treatment and few disease-modifying therapies. The vast majority of AD is late onset (LOAD) without a specific genetic cause, although many genetic and non-genetic risk factors have been identified. One of the most significant modifiable risk factors is diet/lifestyle, with type-2 diabetes mellitus (T2DM) increasing LOAD risk by over 50%. Despite the epidemiological data, the reasons for this link are not understood. Here, we investigated whether altered free fatty acid (FFA) levels seen in T2DM can adversely affect neuronal differentiation, a crucial stage in adult hippocampal neurogenesis (AHN), which is defective in LOAD. We show that chronic exposure of the neuroblastoma cell line, SH-SY5Y to T2DM-relevant levels of the FFAs, oleate and palmitate, profoundly affects the differentiation of these cells. This effect is particularly pronounced for the saturated FFA, palmitate, resulting in neuronal cells of altered morphology, lacking expression of key synaptic markers. We further demonstrate that this exposure dysregulates insulin signalling, GSK3β activity, CDK5 levels and CREB phosphorylation. Crucially, these effects were only observed on exposure during differentiation and can be partially replicated in hiPSC-derived forebrain neurones. Although APP expression is increased by palmitate exposure, there was no increase in secreted or intracellular Aβ, and tau phosphorylation was reduced, implying that these defects are separate from the classical hallmarks of AD. We conclude that long-term, chronic exposure of differentiating neurones induces pathological changes that may explain the link between T2DM and LOAD.

Exploring the green break of season and green date over northern Australia - Rajashree Naha; Tim Cowan; Matthew C. Wheeler; Jyoteshna Owens; David Cobon; Chelsea Jarvis; Peter O’Reagain (Agricultural Systems, 2026)

Combining magnetotelluric, DC resistivity, and time-domain electromagnetic data in geothermal exploration: An example from the M’Deek Geothermal Field in Western British Columbia, Canada - Zoë Vestrum; Martyn J Unsworth; Tim Thompson; David Try (Geothermics, 2025)

Tectonic modulation of caldera volcanism on the South Aegean Volcanic Arc - Abigail Metcalfe; Tim Druitt; Katharina Pank; Steffen Kutterolf; Jonas Preine; Sarah Beethe; Axel Schmitt; Christian Hübscher; Paraskevi Nomikou; Thomas A. Ronge; Carole Berthod; Hehe Chen; et al. (Earth and Planetary Science Letters, 2025)

Circulating biomarkers of infection and endometrial cancer risk - Kara A. Michels; David Jin; Rima Jeske; Jolanta Lissowska; Beata Pepłońska; Nicolas Wentzensen; Tim Waterboer; Britton Trabert (Cancer Causes & Control, 2025)
Purpose Incidence and mortality rates for endometrial cancer are rising. We need to better understand the etiology of this disease and identify new risk factors. We examined whether common genital infections are associated with endometrial cancer. Methods Using serum samples from The Polish Endometrial Cancer Study (443 cases, 443 controls), we measured antibodies against microbial antigens with a multiplex fluorescent bead-based assay. We estimated adjusted odds ratios (OR) and 95% confidence intervals (CI), comparing women with positive versus negative serology. Results Most antibodies were not associated with endometrial cancer overall, but seropositivity for Herpes simplex virus 2 was associated with low-grade tumors (OR 1.43 CI 1.02, 2.00). While increased risks for type II, but not type I tumors, were consistently indicated for multiple Chlamydia trachomatis antigens, most estimates did not reach statistical significance (e.g., Pgp3 seropositivity and type I cancers: OR 0.97 CI 0.73, 1.31; and type II: OR 2.96 CI 0.85, 10.31; heterogeneity p -value = 0.03). The strongest associations for type II tumors were observed with seropositivity for Chlamydial stress response proteins. Conclusion Reproductive tract infections may increase risk for endometrial cancer, but the biologic mechanisms are likely both microbe- and histology-specific. Some C. trachomatis infections may be a risk factor for type II endometrial cancers. Given that so few risk factors for type II endometrial cancers are identified, infection-related mechanisms of carcinogenesis in the endometrium merit continued investigation.

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

The ontogeny of foraging in meerkats, a cooperatively breeding mongoose - Chris Duncan; Zoe Turner; David Gaynor; Jack Thorley; Tim Vink; Tim Clutton-Brock (Animal Behaviour, 2025)

Large cobblestone dams for natural flood management in wide peatland gullies - Adam Ryan Johnston; David Brown; Tim Allott; Salim Goudarzi; Martin Kay; David Milledge; Emma Shuttleworth; Tom Spencer; Martin Evans (Ecological Engineering, 2025)

AIS data underrepresents vessel traffic around coastal Scotland - Emily Hague; Alice Walters; Anna Moscrop; Emma Steel; Katie Dyke; Lauren Hartny-Mills; Alison Lomax; Rebecca Dudley; Pippa Garrard; Jenny Hampson; Sadie Gorvett; Hannah Lightley; et al. (Marine Policy, 2025)

The impact of circular strategies on titanium supply and demand in the aviation industry - Tim Hoff; Benjamin Sprecher; Ahmad Ali Pohya; Gerko Wende; David Peck (Resources, Conservation and Recycling, 2025)

The conservation status of the threatened gazelles of Ar Rub’ al-Khālī, Saudi Arabia - Tim Wacher; Ahmed Alboug; Chris Barichievy; Zaffar Rais Mir; Tom Bruce; David Olson; Rajan Amin (Journal of Arid Environments, 2025)

Using species distribution modelling in identifying locations for habitat restoration, relocations and potential ecological traps for the sand lizard, Lacerta agilis, in Northern Germany - David Bennett; Tim Diekötter (European Journal of Wildlife Research, 2025)
The sand lizard Lacerta agilis is a species of conservation concern in many areas, primarily due to habitat loss and fragmentation. Wildflower compensation areas, an increasingly widespread method of supporting biodiversity in intensive agricultural landscapes, could theoretically support L. agilis but may also act as an ecological trap. Using species distribution modelling, we estimated the relative habitat suitability for L. agilis across Schleswig Holstein. We then performed field studies at 41 wildflower sites (with varying levels of relative suitability) over two years using reptile mats, and a follow up survey with conservation detection dogs at four more sites. Ultimately, no L. agilis were observed at any site, regardless of method. However, the response curves and variable response curves indicate that permanent semi natural habitat has a strong positive influence on relative suitability. This could indicate that longer term measures are a better option for the conservation of this species.

Combining Observations and Models: A Review of the CARDAMOM Framework for Data‐Constrained Terrestrial Ecosystem Modeling - Matthew A. Worden; T. Eren Bilir; A. Anthony Bloom; Jianing Fang; Lily P. Klinek; Alexandra G. Konings; Paul A. Levine; David T. Milodowski; Gregory R. Quetin; T. Luke Smallman; Yinon M. Bar‐On; Renato K. Braghiere; et al. (Global Change Biology, 2025)
The rapid increase in the volume and variety of terrestrial biosphere observations (i.e., remote sensing data and in situ measurements) offers a unique opportunity to derive ecological insights, refine process‐based models, and improve forecasting for decision support. However, despite their potential, ecological observations have primarily been used to benchmark process‐based models, as many past and current models lack the capability to directly integrate observations and their associated uncertainties for parameterization. In contrast, data assimilation frameworks such as the CARbon DAta MOdel fraMework (CARDAMOM) and its suite of process‐based models, known as the Data Assimilation Linked Ecosystem Carbon Model (DALEC), are specifically designed for model‐data fusion. This review, motivated by a recent CARDAMOM community workshop, examines the development and applications of CARDAMOM, with an emphasis on its role in advancing ecosystem process understanding. CARDAMOM employs a Bayesian approach, using a Markov Chain Monte Carlo algorithm to enable data‐driven calibration of DALEC parameters and initial states (i.e., carbon pool sizes) through observation operators. CARDAMOM's unique ability to retrieve localized model process parameters from diverse datasets—ranging from in situ measurements to global satellite observations—makes it a highly flexible tool for analyzing spatially variable ecosystem responses to environmental change. However, assimilating these data also presents challenges, including data quality issues that propagate into model skill, as well as trade‐offs between model complexity, parameter equifinality, and predictive performance. We discuss potential solutions to these challenges, such as reducing parameter equifinality by incorporating new observations. This review also offers community recommendations for incorporating emerging datasets, integrating machine learning techniques, strengthening collaboration with remote sensing, field, and modeling communities, and expanding CARDAMOM's relevance for localized ecosystem monitoring and decision‐making. CARDAMOM enables a deep, mechanistic understanding of terrestrial ecosystem dynamics that cannot be achieved through empirical analyses of observational datasets or weakly constrained models alone.

A case of Plasmodium falciparum malaria presenting 13 years after leaving an endemic area - David Hettle; Mustafa Elsayed; Samuel Mensah; Francesca Neuberger; Debbie Nolder; Hristina Vasileva; Kevin Tetteh; Tim Cutfield; Imogen Jones; Spencer Polley; Louise Turner; Thomas Lavstsen; et al. (Infectious Diseases, 2025)

On solid ground: Assessing the scale-up potential of structural stone in the UK - Charlotte Taylor; Hannah Gold; David Watson; Anthony Darby; Richard Ball; Tim Ibell; Will Hawkins (Resources Policy, 2025)

Future electricity tariffs: designing electricity rates fit for the energy transition - David Ribo-Perez; Christine Gschwendtner; Christian Winzer; Sigurd Bjarghov; Tim Schittekatte; Selin Yilmaz (Energy Policy, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Spatiotemporal changes of atmospheric depositions over 43 years in south-central Ontario - Huaxia Yao; Joelle Young; April James; David Lembcke; Christopher McConnell; Tim Field; Lance Aspden; Sara Rawski; Chris Jones; Michelle Palmer; Claire Holeton; James A. Rusak; et al. (Atmospheric Environment, 2025)

Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

Evaluating initiatives to improve transport justice - Hannah Hook; David Durán-Rodas; Shaila Jamal; Tim Schwanen (Transportation Research Part D: Transport and Environment, 2025)

Evaluation of Six Subgrid-Scale Models for LES of Wind Farms in Stable and Conventionally-Neutral Atmospheric Stratification - Mina Ghobrial; Tim Stallard; David M. Schultz; Pablo Ouro (Boundary-Layer Meteorology, 2025)
The performance of six subgrid-scale (SGS) models is analyzed for large-eddy simulations (LES) of wind-farm flows under stable (SBL) and conventionally-neutral (CNBL) atmospheric conditions. A precursor–concurrent technique is employed to provide fully developed turbulent inflow for simulations of a 40-turbine wind farm. Turbines are represented using the actuator-disc method, employing a baseline grid of 12 cells across the turbine diameter. The SBL precursor flow poses a challenge for LES, as it may not be able to resolve the small turbulent scales featured in this flow if the grid is coarse. For these precursor flows, the baseline grid results of all six SGS models are assessed relative to coarser and finer grids, with 6 and 45 cells across the diameter, respectively. The wall-adapting local eddy-viscosity (WALE) and Lagrangian-averaged scale-dependent dynamic (LASDD) models exhibit high grid sensitivity, while the standard Smagorinsky (Smag.), anisotropic minimum-dissipation (AMD), one-equation turbulent kinetic energy (TKE), and stability-dependent Smagorinsky (SDS) models show low sensitivity. For the wind-farm simulations conducted with the baseline grid, the AMD and SDS models predict similar wind-farm performance. In contrast, the WALE and LASDD models predict nearly 30% less power output, primarily due to their prediction of lower inflow wind speeds. CNBL simulations on the baseline grid show reduced sensitivity to the SGS model due to larger atmospheric turbulence and length scales compared to the SBL flow. Among the six models, the AMD model demonstrates ease of implementation, the least sensitivity to grid size for the SBL precursor flow, and predictions that are consistent with other models and higher-order pseudo-spectral LES solvers, making it a suitable choice for LES of wind-farm flows under both stable and conventionally-neutral conditions.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

The gender wage gap across life: Effects of genetic predisposition towards higher educational attainment - Alex Bryson; Tim Morris; David Bann; David Wilkinson (Economics & Human Biology, 2025)

Metastasis-directed stereotactic radiotherapy in patients with breast cancer: results of an international multicenter cohort study - Alexander Fabian; Daniel Buergy; Fabian Weykamp; Juliane Hörner-Rieber; Denise Bernhardt; Judit Boda-Heggemann; Montserrat Pazos; Nora Mehrhof; David Kaul; Alicia S. Bicu; Eugenia Vlaskou Badra; Susanne Rogers; et al. (Clinical & Experimental Metastasis, 2025)
Metastasis-directed therapy (MDT) for oligometastatic breast cancer (≤ 5 metastases) has shown little effect in specific scenarios of randomized trials. Therefore, we aimed to assess outcomes after metastasis-directed stereotactic radiotherapy (SRT) in various clinical scenarios. We conducted an international retrospective cohort study in thirteen centers including breast cancer patients receiving SRT to any metastatic site. Outcomes included local recurrence (LR), progression-free survival (PFS), and overall survival (OS). Cumulative incidence analysis was used for LR, Kaplan–Meier estimates for PFS and OS. Covariables included patient, disease, and SRT characteristics. We performed univariable and multivariable analyses (MVA). Among 444 patients, 751 metastases were treated with SRT. Of these, 73% were intracranial and 27% extracranial lesions. Oligometastatic disease (OMD) was present in 66% of the patients. LR after two years occurred significantly more often in intracranial (25%) versus extracranial lesions (7%). In MVA of patients with OMD treated for intracranial sites, higher performance status was significantly associated with longer PFS. Further, higher performance status, biologic subtype (HR-pos./HER2-pos.), and MDT to all sites were significantly associated with longer OS. In MVA of oligometastatic patients treated for extracranial sites, biologic subtype (HR-neg./HER2-pos.) and synchronous metastasis were associated with significantly longer PFS, whereas higher grading was associated with significantly shorter PFS. Moreover, biologic subtype (HR-neg./HER2-neg.) was associated with significantly shorter OS. In conclusion, the role of MDT for breast cancer may vary per clinical scenario. Patients with OMD treated for intracranial lesions who had MDT to all sites showed superior OS. Our results should be validated prospectively.

A computational framework to support probabilistic criticality modelling for the geological disposal of radioactive waste - E. Adam Paxton; Jiejie Wu; Tim Hicks; Slimane Doudou; David Applegate; Robert Mason; Andrew Price; Liam Payne (Annals of Nuclear Energy, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Apples to apples: Accurately assessing corporate carbon performance - David Bendig; Colin Schulz; Florent Erbar; Tim Heubeck (Journal of Cleaner Production, 2025)

Field evaluation of the efficacy of passive radiative cooling infrastructure: A case study in Phoenix Arizona - David J. Sailor; Gina Fagliarone; Tim Hebrink; Deepak Amaripadath (Building and Environment, 2025)

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

What do you mean 'Climate Change'? An analysis of climate change framings in three climate assemblies - Corinna Zeitfogel; Tim Daw; David Collste (Environmental Science & Policy, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

An overview of cellulose aerogels and foams for oil sorption: Preparation, modification, and potential of 3D printing - Ang Li; Tim Huber; David Barker; Ali Reza Nazmi; Hossein Najaf Zadeh (Carbohydrate Polymers, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Cell Painting unravels insecticidal modes of action on Spodoptera frugiperda insect cells - Franziska A. Hecker; Bruno Leggio; Tim König; Vladislav Kim; Marc Osterland; David Gnutt; Karsten Niehaus; Sven Geibel (Pesticide Biochemistry and Physiology, 2024)

Self-swabbing versus assisted swabbing for viral detection by qRT-PCR: the experience from SARS-CoV-2 based on a meta-analysis of six prospectively designed evaluations conducted in a UK setting - Tom Fowler; David Chapman; Matthias E. Futschik; Sarah A. Tunkel; Edward Blandford; Elena Turek; Olumide Kolade; Sergio Souza da Cunha; Andrew Dodgson; Paul Klapper; Malur Sudhanva; Lindsey Davies; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose In April 2020, the UK Government implemented NHS Test and Trace to provide SARS-CoV-2 quantitative reverse transcription polymerase chain reaction (qRT-PCR) testing for the public, with nose-and-throat swabbing for samples performed by trained staff. Self-swabbing (SS) would allow rapid scale-up of testing capacity and access. Six studies were undertaken to determine whether SS was as effective for detecting SARS-CoV-2 as swabbing performed by trained staff. Methods Six prospective studies were conducted between April–October 2020, using six swab/media combinations. Differences between assisted swabbing (AS) and SS were evaluated for concordance, positivity, sensitivity, cycle threshold (Ct) values and void rates. Statistical analysis was performed using 95% confidence intervals (CIs), paired t-tests and model-based methods. Results Overall, 3,253 individuals were recruited (median age 37 years, 49% female), with 2,933 having valid paired qRT-PCR results. Pooled concordance rate was 98% (95% CI: 96%, 99%). Positivity rate differences for SS (8.1%) and AS (8.4%) and differences in pooled sensitivities between SS (86%; 95% CI: 78%, 92%) and AS (91%; 95% CI: 78%, 96%) were nonsignificant. Both types of swabbing led to pooled void rates below 2% and strongly correlated Ct values. Age, sex and previous swabbing experience did not have a significant impact on concordance or sensitivity. Conclusion The UK adopted a policy to promote self-testing for SARS-CoV-2 based on data demonstrating equivalence of SS versus AS. Positive outcomes with SS are likely generalisable to testing for other respiratory pathogens, and we consider self-sampling and self-testing essential for future pandemic preparedness.

Review of trace organic chemicals in urban stormwater: Concentrations, distributions, risks, and drivers - Kefeng Zhang; Zhaozhi Zheng; Lena Mutzner; Baiqian Shi; David McCarthy; Pierre Le-Clech; Stuart Khan; Tim D. Fletcher; Marty Hancock; Ana Deletic (Water Research, 2024)

Unified 200 kyr paleohydrologic history of the Southern Great Basin: Death Valley, Searles Valley, Owens Valley and the Devils Hole cave - Tim K. Lowenstein; Kristian J. Olson; Brian W. Stewart; David McGee; Justin S. Stroup; Adam M. Hudson; Kathleen A. Wendt; Mark D. Peaple; Sarah J. Feakins; Tripti Bhattacharya; Steve Lund (Quaternary Science Reviews, 2024)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Benefits of calorie restriction in mice are mediated via energy imbalance, not absolute energy or protein intake - Daniel L. Smith; Sharon E. Mitchell; Maria S. Johnson; Victoria K. Gibbs; Stephanie Dickinson; Beate Henschel; Rui Li; Kathryn A. Kaiser; Daniella E. Chusyd; Andrew W. Brown; David B. Allison; John R. Speakman; et al. (GeroScience, 2024)
Caloric restriction (CR) results in reduced energy and protein intake, raising questions about protein restriction’s contribution to CR longevity benefits. We kept ad libitum ( AL )–fed male C57BL/6J mice at 27°C (AL27) and pair-fed (PF) mice at 22°C (22(PF27)). The 22(PF27) group was fed to match AL27 while restricted for calories due to cold-induced metabolism. The 22(PF27) mice had significantly lower body weight, lean mass, fat mass, leptin, IGF-1, and TNF-α levels than AL27 mice ( p <0.001 for all). Manipulations over ~11 weeks resulted in significant differences in body temperature, physical activity, and expression of key genes linked to hunger in the hypothalamus. Survival was significantly greater in 22(PF27) compared to AL27 overall ( p <0.001). CR in the context of equivalent energy and protein intake resulted in hormonal, metabolic, and physiological benefits and extended longevity. Hence, energy imbalance, rather than low energy or protein intake per se, mediates the benefits of CR.

Evaluation and instantiation of a generic process model for early-stage sustainable product-service system design within three manufacturing companies - David Sarancic; Daniela C.A. Pigosso; Tim C. McAloone (Journal of Cleaner Production, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Influence of 8-weeks of supervised static stretching or resistance training of pectoral major muscles on maximal strength, muscle thickness and range of motion - Tim Wohlann; Konstantin Warneke; Vincent Kalder; David G. Behm; Tobias Schmidt; Stephan Schiemann (European Journal of Applied Physiology, 2024)
Objectives Current research suggests static stretch-induced maximal strength increases and muscle hypertrophy with potential to substitute resistance-training routines. However, most studies investigated the plantar flexors. This study explored the effects of a static stretching program on maximal strength, hypertrophy and flexibility of the pectoralis major and compared the effects with those of traditional resistance training. Methods Eighty-one (81) active participants were allocated to either a static stretching, strength-training or control group. Pectoralis stretching was applied 15 min/day, 4 days per week for 8 weeks, while resistance training trained 3 days per week, 5 × 12 repetitions. Results There was an increase in all parameters (strength: p < 0.001, ƞ 2 = 0.313, muscle thickness: p < 0.001, ƞ 2 = 0.157–0.264, flexibility: p < 0.001, ƞ 2 = 0.316) and a time*group interaction (strength: p = 0.001, ƞ 2 = 0.154, muscle thickness: p = 0.008–0.001, ƞ 2 = 0.117–0.173, flexibility: p < 0.001, ƞ 2 = 0.267). Post-hoc testing showed no difference between both intervention groups regarding maximal strength and muscle thickness ( p = 0.905–0.983, d = 0.036–0.087), while flexibility increased in the stretching group ( p = 0.001, d = 0.789). Conclusion Stretching showed increases in maximal strength and hypertrophy, which were comparable with commonly used resistance training. Based on current literature, the influence of mechanical tension as the underlying mechanism is discussed. Furthermore, as equipment and comparatively long stretching durations are requested to induce meaningful strength increases in recreationally active participants, practical application seems limited to special circumstances.

Sport events and the environment: Assessing the carbon footprint of spectators’ modal choices at professional football games in Austria - David M. Herold; Tim Breitbarth; Anja Hergesell; Nico Schulenkorf (Journal of Cleaner Production, 2024)

Cross-scale and integrative prioritization of multi-functionality in large river floodplains - Martin Tschikof; Barbara Stammel; Gabriele Weigelhofer; Elisabeth Bondar-Kunze; Gabriela Costea; Martin Pusch; Zorica Srdević; Pavel Benka; David Bela Vizi; Tim Borgs; Thomas Hein (Journal of Environmental Management, 2024)

Corrigendum to “Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate” [Agricultural Systems 214 (2024) 1–13/103838] - Duc-Anh An-Vo; David Cobon; Jyoteshna Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

Climate change disrupts the seasonal coupling of plant and soil microbial nutrient cycling in an alpine ecosystem - Arthur A. D. Broadbent; Lindsay K. Newbold; William J. Pritchard; Antonios Michas; Tim Goodall; Irene Cordero; Andrew Giunta; Helen S. K. Snell; Violette V. L. H. Pepper; Helen K. Grant; David X. Soto; Ruediger Kaufmann; et al. (Global Change Biology, 2024)
The seasonal coupling of plant and soil microbial nutrient demands is crucial for efficient ecosystem nutrient cycling and plant production, especially in strongly seasonal alpine ecosystems. Yet, how these seasonal nutrient cycling processes are modified by climate change and what the consequences are for nutrient loss and retention in alpine ecosystems remain unclear. Here, we explored how two pervasive climate change factors, reduced snow cover and shrub expansion, interactively modify the seasonal coupling of plant and soil microbial nitrogen (N) cycling in alpine grasslands, which are warming at double the rate of the global average. We found that the combination of reduced snow cover and shrub expansion disrupted the seasonal coupling of plant and soil N‐cycling, with pronounced effects in spring (shortly after snow melt) and autumn (at the onset of plant senescence). In combination, both climate change factors decreased plant organic N‐uptake by 70% and 82%, soil microbial biomass N by 19% and 38% and increased soil denitrifier abundances by 253% and 136% in spring and autumn, respectively. Shrub expansion also individually modified the seasonality of soil microbial community composition and stoichiometry towards more N‐limited conditions and slower nutrient cycling in spring and autumn. In winter, snow removal markedly reduced the fungal:bacterial biomass ratio, soil N pools and shifted bacterial community composition. Taken together, our findings suggest that interactions between climate change factors can disrupt the temporal coupling of plant and soil microbial N‐cycling processes in alpine grasslands. This could diminish the capacity of these globally widespread alpine ecosystems to retain N and support plant productivity under future climate change.

Phytosiderophore pathway response in barley exposed to iron, zinc or copper starvation - David Aleksza; Andreea Spiridon; Mika Tarkka; Marie-Theres Hauser; Stephan Hann; Tim Causon; Nicolas Kratena; Christian Stanetty; Timothy S. George; Joanne Russell; Eva Oburger (Plant Science, 2024)

Simulation of groundwater-flow dynamics in the U.S. Northern High Plains driven by multi-model estimates of surficial aquifer recharge - Farshid Felfelani; Joseph Hughes; Fei Chen; Aubrey Dugger; Tim Schneider; David Gochis; Jonathan Traylor; Hedeff Essaid (Journal of Hydrology, 2024)

Constraints from lamprophyre petrogenesis on the timing of Eocene lithospheric thinning and associated rifting of Borneo and Sulawesi - David Murphy; Tim A. Moore; D. Hendra Amijaya; Ferian Anggara; Mike Friederich; Carmen Gaina; Jessica Trofimovs; Hayden Dalton; Edafe Ominigbo (Journal of Asian Earth Sciences, 2024)

Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate - Duc-Anh An-Vo; David Cobon; Jo Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

New supporting data to guide the use of evident toxicity in acute oral toxicity studies (OECD TG 420) - Fiona Sewell; Ian Ragan; Graham Horgan; David Andrew; Thomas Holmes; Irene Manou; Boris P. Müller; Tim Rowan; Barbara G. Schmitt; Marco Corvaro (Regulatory Toxicology and Pharmacology, 2024)

Cellular communication among smooth muscle cells: The role of membrane potential via connexins - Chun Xiao; Yishui Sun; Huaxiong Huang; Xingye Yue; Zilong Song; Tim David; Shixin Xu (Journal of Theoretical Biology, 2024)

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Toxicological assessment of E-cigarette flavored E-liquids aerosols using Calu-3 cells: A 3D lung model approach - Felix Effah; John Adragna; David Luglio; Alexis Bailey; Tim Marczylo; Terry Gordon (Toxicology, 2023)

Retrospective spatiotemporal study of antidepressants in Slovenian wastewaters - Maria Laimou-Geraniou; Maarten Quireyns; Tim Boogaerts; Natan Van Wichelen; David Heath; Alexander L.N. van Nuijs; Adrian Covaci; Ester Heath (Science of The Total Environment, 2023)

Effects of management objectives and rules on marine conservation outcomes - Natalie C. Ban; Emily S. Darling; Georgina G. Gurney; Whitney Friedman; Stacy D. Jupiter; W. Peni Lestari; Irfan Yulianto; Sinta Pardede; Sukma A. R. Tarigan; Puji Prihatiningsih; Sangeeta Mangubhai; Waisea Naisilisili; et al. (Conservation Biology, 2023)
Understanding the relative effectiveness and enabling conditions of different area‐based management tools is essential for supporting efforts that achieve positive biodiversity outcomes as area‐based conservation coverage increases to meet newly set international targets. We used data from a coastal social–ecological monitoring program in 6 Indo‐Pacific countries to analyze whether social, ecological, and economic objectives and specific management rules (temporal closures, fishing gear‐specific, species‐specific restrictions) were associated with coral reef fish biomass above sustainable yield levels across different types of area‐based management tools (i.e., comparing those designated as marine protected areas [MPAs] with other types of area‐based management). All categories of objectives, multiple combinations of rules, and all types of area‐based management had some sites that were able to sustain high levels of reef fish biomass—a key measure for coral reef functioning—compared with reference sites with no area‐based management. Yet, the same management types also had sites with low biomass. As governments advance their commitments to the Kunming–Montreal Global Biodiversity Framework and the target to conserve 30% of the planet's land and oceans by 2030, we found that although different types of management can be effective, most of the managed areas in our study regions did not meet criteria for effectiveness. These findings underscore the importance of strong management and governance of managed areas and the need to measure the ecological impact of area‐based management rather than counting areas because of their designation.

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Peatland gully restoration with stone and timber dams (Kinder Plateau, UK) - Tim Howson; Martin Evans; Tim Allott; Emma Shuttleworth; Adam Johnston; Joe Rees; David Milledge; Donald Edokpa; Chris Lockyer; Martin Kay; Tom Spencer; David Brown; et al. (Ecological Engineering, 2023)

Accelerating ocean species discovery and laying the foundations for the future of marine biodiversity research and monitoring - Alex David Rogers; Hannah Appiah-Madson; Jeff A. Ardron; Nicholas J. Bax; Punyasloke Bhadury; Angelika Brandt; Pier-Luigi Buttigieg; Olivier De Clerck; Claudia Delgado; Daniel L. Distel; Adrian Glover; Judith Gobin; et al. (Frontiers in Marine Science, 2023)
Ocean Census is a new Large-Scale Strategic Science Mission aimed at accelerating the discovery and description of marine species. This mission addresses the knowledge gap of the diversity and distribution of marine life whereby of an estimated 1 million to 2 million species of marine life between 75% to 90% remain undescribed to date. Without improved knowledge of marine biodiversity, tackling the decline and eventual extinction of many marine species will not be possible. The marine biota has evolved over 4 billion years and includes many branches of the tree of life that do not exist on land or in freshwater. Understanding what is in the ocean and where it lives is fundamental science, which is required to understand how the ocean works, the direct and indirect benefits it provides to society and how human impacts can be reduced and managed to ensure marine ecosystems remain healthy. We describe a strategy to accelerate the rate of ocean species discovery by: 1) employing consistent standards for digitisation of species data to broaden access to biodiversity knowledge and enabling cybertaxonomy; 2) establishing new working practices and adopting advanced technologies to accelerate taxonomy; 3) building the capacity of stakeholders to undertake taxonomic and biodiversity research and capacity development, especially targeted at low- and middle-income countries (LMICs) so they can better assess and manage life in their waters and contribute to global biodiversity knowledge; and 4) increasing observational coverage on dedicated expeditions. Ocean Census, is conceived as a global open network of scientists anchored by Biodiversity Centres in developed countries and LMICs. Through a collaborative approach, including co-production of science with LMICs, and by working with funding partners, Ocean Census will focus and grow current efforts to discover ocean life globally, and permanently transform our ability to document, describe and safeguard marine species.

Honey bee drones are synchronously hyperactive inside the nest - Louisa C. Neubauer; Jacob D. Davidson; Benjamin Wild; David M. Dormagen; Tim Landgraf; Iain D. Couzin; Michael L. Smith (Animal Behaviour, 2023)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand indicate biodiversity change - Irene Middleton; Malcolm Francis; J. David Aguirre; Carl Struthers; Thomas Trnski; Clinton Duffy; John Anderson; Mary Carney; Nathan Cox; Stephen Hemstalk; Blair Herbert; Craig Johnston; et al. (Journal of Biogeography, 2023)
Aim Climate change is driving biogeographic change globally, including poleward range shifts of species and the increasing abundance of rare species. We examine spatiotemporal patterns in the occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand to determine whether biodiversity change is occurring in this temperate region and to set a baseline for future monitoring of climate change impacts. Location Aotearoa New Zealand (NZ). Taxon Marine fishes. Methods We consolidated 100 years of unpublished records and citizen science sightings of tropical, subtropical and rare fishes to develop a focal species database for NZ. Using hotspot analysis, we identified geographic locations where the occurrence and diversity of focal species is greater than expected. We examine the spatiotemporal variation in hotspots by focal species lifestage, habitat and taxonomic family. Results Focal species occurrences and diversity in NZ have increased. We present 17 new‐to‐NZ marine fish species, and a new‐to‐NZ family. Focal species now account for 6.5% of pelagic fishes and 17.3% of benthic fishes in NZ. The northeast of the North Island (Te Ika‐a‐Māui) was a consistent hotspot of focal species occurrences and diversity. Hotspots of mature and pelagic fish occurrences appeared further south than juvenile and benthic species occurrences. Families with tropical affinities (Labridae and Pomacentridae) were restricted to northeastern NZ whereas hotspots of families with temperate affinities (i.e. Cheilodactylidae) extended into the South Island (Te Waipounamu). Main Conclusions Tropical, subtropical and rare fishes are a major component of the fish biodiversity in temperate NZ, and their occurrences and diversity has increased over the past half‐century. Northeastern NZ consistently has the highest occurrence rate and diversity of warmer‐water fishes. Our study demonstrates the value in consolidating citizen scientist observations to detect biodiversity change, and to inform current baselines and future monitoring of climate‐related biodiversity change.

Global prevalence of setting longlines at dawn highlights bycatch risk for threatened albatross - David Kroodsma; Joanna Turner; Cian Luck; Tim Hochberg; Nathan Miller; Philip Augustyn; Stephanie Prince (Biological Conservation, 2023)

Ionosphere variability I: Advances in observational, monitoring and detection capabilities - Ioanna Tsagouri; Anna Belehaki; David R. Themens; Norbert Jakowski; Tim Fuller-Rowell; Mainul M. Hoque; Grzegorz Nykiel; Wojciech J. Miloch; Claudia Borries; Anna Morozova; Teresa Barata; William Engelke; et al. (Advances in Space Research, 2023)

Measuring riverine macroplastic: Methods, harmonisation, and quality control - Rachel Hurley; Hans Fredrik Veiteberg Braaten; Luca Nizzetto; Eirik Hovland Steindal; Yan Lin; François Clayer; Tim van Emmerik; Nina Tuscano Buenaventura; David Petersen Eidsvoll; Asle Økelsrud; Magnus Norling; Hans Nicolai Adam; et al. (Water Research, 2023)

Rhenium mineral resources: A global assessment - Tim T. Werner; Gavin M. Mudd; Simon M. Jowitt; David Huston (Resources Policy, 2023)

Failure of an attempt to eradicate southern sting nematode (Ibipora lolii) from the Brisbane Cricket Ground (the Gabba) - Graham R Stirling; Wayne O’Neill; Jennifer Cobon; Tim Shuey; David Sandurski (Australasian Plant Pathology, 2023)

Inflammation and vascular remodeling in COVID-19 hearts - Christopher Werlein; Maximilian Ackermann; Helge Stark; Harshit R. Shah; Alexandar Tzankov; Jasmin Dinonne Haslbauer; Saskia von Stillfried; Roman David Bülow; Ali El-Armouche; Stephan Kuenzel; Jan Lukas Robertus; Marius Reichardt; et al. (Angiogenesis, 2023)
A wide range of cardiac symptoms have been observed in COVID-19 patients, often significantly influencing the clinical outcome. While the pathophysiology of pulmonary COVID-19 manifestation has been substantially unraveled, the underlying pathomechanisms of cardiac involvement in COVID-19 are largely unknown. In this multicentre study, we performed a comprehensive analysis of heart samples from 24 autopsies with confirmed SARS-CoV-2 infection and compared them to samples of age-matched Influenza H1N1 A ( n = 16), lymphocytic non-influenza myocarditis cases ( n = 8), and non-inflamed heart tissue ( n = 9). We employed conventional histopathology, multiplexed immunohistochemistry (MPX), microvascular corrosion casting, scanning electron microscopy, X-ray phase-contrast tomography using synchrotron radiation, and direct multiplexed measurements of gene expression, to assess morphological and molecular changes holistically. Based on histopathology, none of the COVID-19 samples fulfilled the established diagnostic criteria of viral myocarditis. However, quantification via MPX showed a significant increase in perivascular CD11b/TIE2 + —macrophages in COVID-19 over time, which was not observed in influenza or non-SARS-CoV-2 viral myocarditis patients. Ultrastructurally, a significant increase in intussusceptive angiogenesis as well as multifocal thrombi, inapparent in conventional morphological analysis, could be demonstrated. In line with this, on a molecular level, COVID-19 hearts displayed a distinct expression pattern of genes primarily coding for factors involved in angiogenesis and epithelial-mesenchymal transition (EMT), changes not seen in any of the other patient groups. We conclude that cardiac involvement in COVID-19 is an angiocentric macrophage-driven inflammatory process, distinct from classical anti-viral inflammatory responses, and substantially underappreciated by conventional histopathologic analysis. For the first time, we have observed intussusceptive angiogenesis in cardiac tissue, which we previously identified as the linchpin of vascular remodeling in COVID-19 pneumonia, as a pathognomic sign in affected hearts. Moreover, we identified CD11b + /TIE2 + macrophages as the drivers of intussusceptive angiogenesis and set forward a putative model for the molecular regulation of vascular alterations.

Grazing patterns, diet quality, and performance of cow-calf pairs using continuous or rotational grazing in the Texas panhandle USA - Larry D. Fritzler; Tim J. Steffens; Marty B. Rhoades; David G. Lust (Journal of Arid Environments, 2023)

Designing sustainable product-service systems: A generic process model for the early stages - David Sarancic; Daniela C.A. Pigosso; Giuditta Pezzotta; Fabiana Pirola; Tim C. McAloone (Sustainable Production and Consumption, 2023)

Soil organic carbon stocks by soil group for afforested soils in Ireland - Caren Jarmain; Thomas Cummins; Antonio Jonay Jovani-Sancho; Tim Nairn; Alina Premrov; Brian Reidy; Florence Renou-Wilson; Brian Tobin; Kilian Walz; David Wilson; Kenneth A. Byrne (Geoderma Regional, 2023)

Extremely rapid, Lagrangian modeling of 2D flooding: A rivulet-based approach - W. Brent Daniel; Corinne Roth; Xue Li; Cindy Rakowski; Tim McPherson; David Judi (Environmental Modelling & Software, 2023)

Abundance trends for river macroinvertebrates vary across taxa, trophic group and river typology - Kathryn E. Powell; Tom H. Oliver; Tim Johns; Manuela González‐Suárez; Judy England; David B. Roy (Global Change Biology, 2023)
There is mounting evidence that terrestrial arthropods are declining rapidly in many areas of the world. It is unclear whether freshwater invertebrates, which are key providers of ecosystem services, are also declining. We addressed this question by analysing a long‐term dataset of macroinvertebrate abundance collected from 2002 to 2019 across 5009 sampling sites in English rivers. Patterns varied markedly across taxonomic groups. Within trophic groups we detected increases in the abundance of carnivores by 19% and herbivores by 14.8%, while we estimated decomposers have declined by 21.7% in abundance since 2002. We also found heterogeneity in trends across rivers belonging to different typologies based on geological dominance and catchment altitude, with organic lowland rivers having generally higher rates of increase in abundance across taxa and trophic groups, with siliceous lowland rivers having the most declines. Our results reveal a complex picture of change in freshwater macroinvertebrate abundance between taxonomic groups, trophic levels and river typologies. Our analysis helps with identifying priority regions for action on potential environmental stressors where we discover macroinvertebrate abundance declines.

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Sediment gravity flow frequency offshore central California diminished significantly following the Last Glacial Maximum - Stephen C. Dobbs; Charles K. Paull; Eve M. Lundsten; Roberto Gwiazda; David W. Caress; Mary McGann; Marianne M. Coholich; Maureen A. L. Walton; Nora M. Nieminski; Tim McHargue; Stephan A. Graham (Frontiers in Marine Science, 2023)
A high-resolution multibeam survey from a portion of the San Simeon Channel (offshore Morro Bay, California) captured a zone of recurring troughs and ridges adjacent to prominent submarine meander bends. Through an integrated study using surveying data, sediment core analysis, radiocarbon dating, and stable isotope measurements, we hypothesize that turbidity current event frequency was higher during the late Pleistocene than at present conditions. We speculate that the rise in sea-level following the Last Glacial Maximum sequestered sedimentation largely to the shelf during the Holocene. This work suggests that the occurrence of sediment gravity flows in this region, particularly away from any submarine channels, is appreciably lower than at times of continental shelf subaerial exposure.

Chemostratigraphic and mineralogical examination of the Kilwa Group claystones, coastal Tanzania: An alternative approach to refine the lithostratigraphy - Ross McCabe; Christopher J. Nicholas; Bill Fitches; David Wray; Tim Pearce (Journal of African Earth Sciences, 2023)

Application of Brillouin thermometry to latest Pleistocene and Holocene halite from Searles Lake, California, USA - Kristian J. Olson; Emmanuel Guillerm; Mark D. Peaple; Tim K. Lowenstein; Véronique Gardien; Frédéric Caupin; Sarah J. Feakins; Jessica E. Tierney; Justin Stroup; Steve Lund; David McGee (Earth and Planetary Science Letters, 2023)

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

A solution for autonomous, adaptive monitoring of coastal ocean ecosystems: Integrating ocean robots and operational forecasts - David A. Ford; Shenan Grossberg; Gianmario Rinaldi; Prathyush P. Menon; Matthew R. Palmer; Jozef Skákala; Tim Smyth; Charlotte A. J. Williams; Alvaro Lorenzo Lopez; Stefano Ciavatta (Frontiers in Marine Science, 2022)
This study presents a proof-of-concept for a fully automated and adaptive observing system for coastal ocean ecosystems. Such systems present a viable future observational framework for oceanography, reducing the cost and carbon footprint of marine research. An autonomous ocean robot (an ocean glider) was deployed for 11 weeks in the western English Channel and navigated by exchanging information with operational forecasting models. It aimed to track the onset and development of the spring phytoplankton bloom in 2021. A stochastic prediction model combined the real-time glider data with forecasts from an operational numerical model, which in turn assimilated the glider observations and other environmental data, to create high-resolution probabilistic predictions of phytoplankton and its chlorophyll signature. A series of waypoints were calculated at regular time intervals, to navigate the glider to where the phytoplankton bloom was most likely to be found. The glider successfully tracked the spring bloom at unprecedented temporal resolution, and the adaptive sampling strategy was shown to be feasible in an operational context. Assimilating the real-time glider data clearly improved operational biogeochemical forecasts when validated against independent observations at a nearby time series station, with a smaller impact at a more distant neighboring station. Remaining issues to be addressed were identified, for instance relating to quality control of near-real time data, accounting for differences between remote sensing and in situ observations, and extension to larger geographic domains. Based on these, recommendations are made for the development of future smart observing systems.

Ecological consequences of historic moorland ‘improvement’ - Francis M. Rowney; Ralph M. Fyfe; Philip Anderson; Robert Barnett; William Blake; Tim Daley; Katie Head; Alison MacLeod; Ian Matthews; David N. Smith (Biodiversity and Conservation, 2022)

Site formation processes of outdoor spaces in tropical environments: A micro-geoarchaeological case study from backyard Lo Gach, southern Vietnam - Elle Grono; David E. Friesem; Rachel Wood; Tim Denham; Nguyen Khanh Trung Kien; Dang Ngoc Kinh; Philip J. Piper (Archaeological and Anthropological Sciences, 2022)

Temperature variability interacts with mean temperature to influence the predictability of microbial phenotypes - Fei‐Xue Fu; Bernhard Tschitschko; David A. Hutchins; Michaela E. Larsson; Kirralee G. Baker; Allison McInnes; Tim Kahlke; Arjun Verma; Shauna A. Murray; Martina A. Doblin (Global Change Biology, 2022)
Despite their relatively high thermal optima ( T opt ), tropical taxa may be particularly vulnerable to a rising baseline and increased temperature variation because they live in relatively stable temperatures closer to their T opt . We examined how microbial eukaryotes with differing thermal histories responded to temperature fluctuations of different amplitudes (0 control, ±2, ±4°C) around mean temperatures below or above their T opt . Cosmopolitan dinoflagellates were selected based on their distinct thermal traits and included two species of the same genus (tropical and temperate Coolia spp.), and two strains of the same species maintained at different temperatures for >500 generations (tropical Amphidinium massartii control temperature and high temperature, CT and HT, respectively). There was a universal decline in population growth rate under temperature fluctuations, but strains with narrower thermal niche breadth (temperate Coolia and HT) showed ~10% greater reduction in growth. At suboptimal mean temperatures, cells in the cool phase of the fluctuation stopped dividing, fixed less carbon (C) and had enlarged cell volumes that scaled positively with elemental C, N, and P and C:Chlorophyll‐ a . However, at a supra‐optimal mean temperature, fixed C was directed away from cell division and novel trait combinations developed, leading to greater phenotypic diversity. At the molecular level, heat‐shock proteins, and chaperones, in addition to transcripts involving genome rearrangements, were upregulated in CT and HT during the warm phase of the supra‐optimal fluctuation (30 ± 4°C), a stress response indicating protection. In contrast, the tropical Coolia species upregulated major energy pathways in the warm phase of its supra‐optimal fluctuation (25 ± 4°C), indicating a broadscale shift in metabolism. Our results demonstrate divergent effects between taxa and that temporal variability in environmental conditions interacts with changes in the thermal mean to mediate microbial responses to global change, with implications for biogeochemical cycling.

Response of the plant core microbiome to Fusarium oxysporum infection and identification of the pathobiome - Zhiguang Qiu; Jay Prakash Verma; Hongwei Liu; Juntao Wang; Bruna D. Batista; Simranjit Kaur; Arthur Prudêncio de Araujo Pereira; Catriona A. Macdonald; Pankaj Trivedi; Tim Weaver; Warren C. Conaty; David T. Tissue; et al. (Environmental Microbiology, 2022)
Plant core microbiomes consist of persistent key members that provide critical host functions, but their assemblages can be interrupted by biotic and abiotic stresses. The pathobiome is comprised of dynamic microbial interactions in response to disease status of the host. Hence, identifying variation in the core microbiome and pathobiome can significantly advance our understanding of microbial–microbial interactions and consequences for disease progression and host functions. In this study, we combined glasshouse and field studies to analyse the soil and plant rhizosphere microbiome of cotton plants ( Gossypium hirsutum ) in the presence of a cotton‐specific fungal pathogen, Fusarium oxysporum f. sp. vasinfectum (FOV). We found that FOV directly and consistently altered the rhizosphere microbiome, but the biocontrol agents enabled microbial assemblages to resist pathogenic stress. Using co‐occurrence network analysis of the core microbiome, we identified the pathobiome comprised of the pathogen and key associate phylotypes in the cotton microbiome. Isolation and application of some negatively correlated pathobiome members provided protection against plant infection. Importantly, our field survey from multiple cotton fields validated the pattern and responses of core microbiomes under FOV infection. This study advances key understanding of core microbiome responses and existence of plant pathobiomes, which provides a novel framework to better manage plant diseases in agriculture and natural settings.

The Effect of Mindfulness-based Programs on Cognitive Function in Adults: A Systematic Review and Meta-analysis - Tim Whitfield; Thorsten Barnhofer; Rebecca Acabchuk; Avi Cohen; Michael Lee; Marco Schlosser; Eider M. Arenaza-Urquijo; Adriana Böttcher; Willoughby Britton; Nina Coll-Padros; Fabienne Collette; Gaël Chételat; et al. (Neuropsychology Review, 2022)
Mindfulness-based programs (MBPs) are increasingly utilized to improve mental health. Interest in the putative effects of MBPs on cognitive function is also growing. This is the first meta-analysis of objective cognitive outcomes across multiple domains from randomized MBP studies of adults. Seven databases were systematically searched to January 2020. Fifty-six unique studies ( n = 2,931) were included, of which 45 ( n = 2,238) were synthesized using robust variance estimation meta-analysis. Meta-regression and subgroup analyses evaluated moderators. Pooling data across cognitive domains, the summary effect size for all studies favored MBPs over comparators and was small in magnitude ( g = 0.15; [0.05, 0.24]). Across subgroup analyses of individual cognitive domains/subdomains, MBPs outperformed comparators for executive function ( g = 0.15; [0.02, 0.27]) and working memory outcomes ( g = 0.23; [0.11, 0.36]) only. Subgroup analyses identified significant effects for studies of non-clinical samples, as well as for adults aged over 60. Across all studies, MBPs outperformed inactive, but not active comparators. Limitations include the primarily unclear within-study risk of bias (only a minority of studies were considered low risk), and that statistical constraints rendered some p -values unreliable. Together, results partially corroborate the hypothesized link between mindfulness practices and cognitive performance. This review was registered with PROSPERO [CRD42018100904].

Long-Term Drought and Warming Alter Soil Bacterial and Fungal Communities in an Upland Heathland - Fiona M. Seaton; Sabine Reinsch; Tim Goodall; Nicola White; Davey L. Jones; Robert I. Griffiths; Simon Creer; Andy Smith; Bridget A. Emmett; David A. Robinson (Ecosystems, 2022)
The response of soil microbial communities to a changing climate will impact global biogeochemical cycles, potentially leading to positive and negative feedbacks. However, our understanding of how soil microbial communities respond to climate change and the implications of these changes for future soil function is limited. Here, we assess the response of soil bacterial and fungal communities to long-term experimental climate change in a heathland organo-mineral soil. We analysed microbial communities using Illumina sequencing of the 16S rRNA gene and ITS2 region at two depths, from plots undergoing 4 and 18 years of in situ summer drought or warming. We also assessed the colonisation of Calluna vulgaris roots by ericoid and dark septate endophytic (DSE) fungi using microscopy after 16 years of climate treatment. We found significant changes in both the bacterial and fungal communities in response to drought and warming, likely mediated by changes in soil pH and electrical conductivity. Changes in the microbial communities were more pronounced after a longer period of climate manipulation. Additionally, the subsoil communities of the long-term warmed plots became similar to the topsoil. Ericoid mycorrhizal colonisation decreased with depth while DSEs increased; however, these trends with depth were removed by warming. We largely ascribe the observed changes in microbial communities to shifts in plant cover and subsequent feedback on soil physicochemical properties, especially pH. Our results demonstrate the importance of considering changes in soil microbial responses to climate change across different soil depths and after extended periods of time.

Extinction risk of the endemic vascular flora of Kauai, Hawaii, based on IUCN assessments - Nina Rønsted; Seana K. Walsh; Margaret Clark; Merlin Edmonds; Tim Flynn; Scott Heintzman; Alexander Loomis; David Lorence; Uma Nagendra; Ben Nyberg; Michael Opgenorth; Lauren Weisenberger; et al. (Conservation Biology, 2022)
The International Union for Conservation of Nature's Red List of Threatened Species (IUCN Red List) is the world's most comprehensive information source on the global conservation status of species. Governmental agencies and conservation organizations increasingly rely on IUCN Red List assessments to develop conservation policies and priorities. Funding agencies use the assessments as evaluation criteria, and researchers use meta‐analysis of red‐list data to address fundamental and applied conservation science questions. However, the circa 143,000 IUCN assessments represent a fraction of the world's biodiversity and are biased in regional and organismal coverage. These biases may affect conservation priorities, funding, and uses of these data to understand global patterns. Isolated oceanic islands are characterized by high endemicity, but the unique biodiversity of many islands is experiencing high extinction rates. The archipelago of Hawaii has one of the highest levels of endemism of any floristic region; 90% of its 1367 native vascular plant taxa are classified as endemic. We used the IUCN's assessment of the complete single‐island endemic (SIE) vascular plant flora of Kauai, Hawaii, to assess the proportion and drivers of decline of threatened plants in an oceanic island setting. We compared the IUCN assessments with federal, state, and other local assessments of Kauai species or taxa of conservation concern. Finally, we conducted a preliminary assessment for all 1044 native vascular plants of Hawaii based on IUCN criterion B by estimating area of occupancy, extent of occurrence, and number of locations to determine whether the pattern found for the SIE vascular flora of Kauai is comparable to the native vascular flora of the Hawaiian Islands. We compared our results with patterns observed for assessments of other floras. According to IUCN, 256 SIE vascular plant taxa are threatened with extinction and 5% are already extinct. This is the highest extinction risk reported for any flora to date. The preliminary assessment of the native vascular flora of Hawaii showed that 72% (753 taxa) is threatened. The flora of Hawaii may be one of the world's most threatened; thus, increased and novel conservation measures in the state and on other remote oceanic islands are urgently needed.

Spatial Distribution and Encounter Rates of Delphinids and Deep Diving Cetaceans in the Eastern Mediterranean Sea of Turkey and the Extent of Overlap With Areas of Dense Marine Traffic - Tim Awbery; Aylin Akkaya; Patrick Lyne; Laura Rudd; Gemma Hoogenstrijd; Madeleine Nedelcu; David Kniha; Mehmet Akif Erdoğan; Cherisse Persad; Ayaka Amaha Öztürk; Bayram Öztürk (Frontiers in Marine Science, 2022)
Marine traffic has been identified as a serious threat to Mediterranean cetaceans with few mitigation strategies in place. With only limited research effort within the Eastern Basin, neither baseline species knowledge nor the magnitude of threats have been comprehensively assessed. Delineating the extent of overlap between marine traffic and cetaceans provides decision makers with important information to facilitate management. The current study employed the first seasonal boat surveys within the Eastern Mediterranean Sea of Turkey, incorporating visual and acoustic survey techniques between 2018 and 2020 to understand the spatial distribution of cetacean species. Additionally, marine traffic density data were retrieved to assess the overlap with marine traffic. Encounter rates of cetaceans and marine traffic density were recorded for each 100 km 2 cell within a grid. Subsequently, encounter and marine traffic density data were used to create a potential risk index to establish where the potential for marine traffic and cetacean overlap was high. Overall, eight surveys were undertaken with a survey coverage of 21,899 km 2 between the Rhodes and Antalya Basins. Deep diving cetaceans (sperm and beaked whales) were detected on 28 occasions, with 166 encounters of delphinids of which bottlenose, striped and common dolphins were visually confirmed. Spatially, delphinids were distributed throughout the survey area but encounter rates for both deep diving cetaceans and delphinids were highest between the Rhodes and Finike Basins. While sperm whales were generally detected around the 1000m contour, delphinids were encountered at varying depths. Overall, two years of monthly marine traffic density were retrieved with an average density of 0.37 hours of monthly vessel activity per square kilometer during the study period. The mean density of vessels was 0.32 and 1.03 hours of monthly vessel activity per square kilometer in non-coastal and coastal waters respectively. The Eastern Mediterranean Sea has several important shipping lanes within the study area. Two priority areas for deep diving cetacean and a large priority area for cetaceans were identified in the waters between Marmaris and Finike where high cetacean encounters and dense marine traffic overlapped. The current study revealed important habitats for cetaceans within the data deficient Eastern Mediterranean Sea and delineated potential risk area where marine traffic should be limited.

Characterisation of the Mouse Cerebellar Proteome in the GFAP-IL6 Model of Chronic Neuroinflammation - Rustam Asgarov; Monokesh K. Sen; Meena Mikhael; Tim Karl; Erika Gyengesi; David A. Mahns; Chandra S. Malladi; Gerald W. Münch (The Cerebellum, 2022)

Agathisflavone Modifies Microglial Activation State and Myelination in Organotypic Cerebellar Slices Culture - Monique Marylin Alves de Almeida; Francesca Pieropan; Tim Footz; Jorge Mauricio David; Juceni Pereira David; Victor Diogenes Amaral da Silva; Cleide dos Santos Souza; Anastassia Voronova; Arthur Morgan Butt; Silvia Lima Costa (Journal of Neuroimmune Pharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

Mesenchymal Stromal Cell‐derived Extracellular Vesicles in Preclinical Animal Models of Tumor Growth: Systematic Review and Meta‐analysis - Adrian J.M. Bailey; Alvin Tieu; Manika Gupta; Mitchell Slobodian; Risa Shorr; Tim Ramsay; Rosendo A. Rodriguez; Dean A. Fergusson; Manoj M. Lalu; David S. Allan (Stem Cell Reviews and Reports, 2022)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Extent and Characteristics of a Newly Discovered Unique Bryozoan Biogenic Reef Complex - Travis Luke Dutka; Alex J. Fejer; Tim Williams; David M. Donnelly; Adrian J. Flynn (Frontiers in Marine Science, 2022)
Using multibeam echosounding (R2Sonic, Austin, Texas) combined with underwater observation and imagery surveys, this study sought to estimate the size and describe the typology of newly discovered biogenic bryozoan reefs in Western Port (VIC, Australia). The bryozoan species forming the biogenic structure are Triphyllozoon moniliferum , T. munitum (both fenestrate forms and dominant on the reef) and Celleporaria (non-fenestrate form and sub-dominant). The bryozoan biogenic reefs occupy a total area of 1.74 km 2 . Their distribution appears to be geomorphically and depth-controlled, which might limit their maximum possible extent. The Western Port bryozoan reefs are unique and globally significant because they: (1) occur in shallow water (typically 5–10 m), (2) are dominated by delicate fenestrate colonies of T. moniliferum and T. munitum , (3) have two distinct morphologies (linear and patch-like), (4) form continuous rows of reef interspersed with fine sediment, and (5) the size and vertical relief (up to approximately 1.5 m) are among the largest recorded in the world. In Western Port, these bryozoan reefs are habitat-forming and may represent sites of enhanced biodiversity, which is currently being investigated in another separate study and are likely important habitat utilised by commercially and recreationally fished species. The bryozoan biogenic reefs are a previously unrecognised feature of conservation significance in this Ramsar site. The reefs are potentially vulnerable to physical damage from recreational fishing practices, sediment smothering and scouring, algal encroachment and hydrological alteration. Recommendations for monitoring and potential management of this unique biotope are made.

Somatosensory perturbations influence cortical activity associated with single-limb balance performance - David A. Sherman; Tim Lehmann; Jochen Baumeister; Dustin R. Grooms; Grant E. Norte (Experimental Brain Research, 2022)

Marine phytoplankton resilience may moderate oligotrophic ecosystem responses and biogeochemical feedbacks to climate change - Adam C. Martiny; George I. Hagstrom; Tim DeVries; Robert T. Letscher; Gregory L. Britten; Catherine A. Garcia; Eric Galbraith; David Karl; Simon A. Levin; Michael W. Lomas; Allison R. Moreno; David Talmy; et al. (Limnology and Oceanography, 2022)
Are the oceans turning into deserts? Rising temperature, increasing surface stratification, and decreasing vertical inputs of nutrients are expected to cause an expansion of warm, nutrient deplete ecosystems. Such an expansion is predicted to negatively affect a trio of key ocean biogeochemical features: phytoplankton biomass, primary productivity, and carbon export. However, phytoplankton communities are complex adaptive systems with immense diversity that could render them at least partially resilient to global changes. This can be illustrated by the biology of the Prochlorococcus “collective.” Adaptations to counter stress, use of alternative nutrient sources, and frugal resource allocation can allow Prochlorococcus to buffer climate‐driven changes in nutrient availability. In contrast, cell physiology is more sensitive to temperature changes. Here, we argue that biogeochemical models need to consider the adaptive potential of diverse phytoplankton communities. However, a full understanding of phytoplankton resilience to future ocean changes is hampered by a lack of global biogeographic observations to test theories. We propose that the resilience may in fact be greater in oligotrophic waters than currently considered with implications for future predictions of phytoplankton biomass, primary productivity, and carbon export.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Shrub expansion modulates belowground impacts of changing snow conditions in alpine grasslands - Arthur A. D. Broadbent; Michael Bahn; William J. Pritchard; Lindsay K. Newbold; Tim Goodall; Andrew Guinta; Helen S. K. Snell; Irene Cordero; Antonios Michas; Helen K. Grant; David X. Soto; Rüdiger Kaufmann; et al. (Ecology Letters, 2022)
Climate change is disproportionately impacting mountain ecosystems, leading to large reductions in winter snow cover, earlier spring snowmelt and widespread shrub expansion into alpine grasslands. Yet, the combined effects of shrub expansion and changing snow conditions on abiotic and biotic soil properties remains poorly understood. We used complementary field experiments to show that reduced snow cover and earlier snowmelt have effects on soil microbial communities and functioning that persist into summer. However, ericaceous shrub expansion modulates a number of these impacts and has stronger belowground effects than changing snow conditions. Ericaceous shrub expansion did not alter snow depth or snowmelt timing but did increase the abundance of ericoid mycorrhizal fungi and oligotrophic bacteria, which was linked to decreased soil respiration and nitrogen availability. Our findings suggest that changing winter snow conditions have cross‐seasonal impacts on soil properties, but shifts in vegetation can modulate belowground effects of future alpine climate change.

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

Correction to: Choose and stay on one out of two paths: distinction between clinical versus research genetic testing to identify cancer predisposition syndromes among patients with cancer - Tim Ripperger; D. Gareth Evans; David Malkin; Christian P. Kratz (Familial Cancer, 2021)

Choose and stay on one out of two paths: distinction between clinical versus research genetic testing to identify cancer predisposition syndromes among patients with cancer - Tim Ripperger; D Gareth Evans; David Malkin; Christian P. Kratz (Familial Cancer, 2021)

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

Steps to diversify priority‐setting research in conservation: reflections on de Gracia 2021 - Tommaso Jucker; Tatsuya Amano; Alexandra Bell; Emma E. Garnett; Jan Laurens Geffert; Miriam K. Guth; Andrew Hacket‐Pain; Sarah H. Luke; Hannah S. Mumby; Matheus Nunes; Tim Rademacher; David C. Rose; et al. (Conservation Biology, 2021)

Understanding the Impact of Soil Clay Mineralogy on the Adsorption Behavior of Zinc - Amir Behroozi; Meenakshi Arora; Tim David Fletcher; Andrew William Western; Justin Francis Costelloe (International Journal of Environmental Research, 2021)

Prospective evaluation of functional brain activity and oxidative damage in breast cancer: changes in task-induced deactivation during a working memory task - James C. Root; Denise Pergolizzi; Hong Pan; Irene Orlow; Steven D. Passik; David Silbersweig; Emily Stern; Tim A. Ahles (Brain Imaging and Behavior, 2021)

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

Towards a more precise – and accurate – view of eco‐evolution - Ronald D. Bassar; Tim Coulson; Joseph Travis; David N. Reznick (Ecology Letters, 2021)
Over the past 15 years, the number of papers focused on ‘eco‐evo dynamics’ has increased exponentially (Figure 1 ). This pattern suggests the rapid growth of a new, integrative discipline. We argue this overstates the case. First, the terms ‘eco‐evo dynamics’ and ‘eco‐evo interactions’ are used too imprecisely. As a result, many studies that claim to describe eco‐evo dynamics are actually describing basic ecological or evolutionary processes. Second, these terms are often used as if the study of how ecological and evolutionary processes are intertwined is novel when, in fact, it is not. The result is confusion over what the term ‘eco‐evolution’ and its derivatives describe. We advocate a more precise definition of eco‐evolution that is more useful in efforts to understand and characterise the diversity of ecological and evolutionary processes and that focuses attention on the subset of those processes that occur only when ecological and evolutionary timescales are comparable. Number of papers returned, by year, by a search in Web of Science with the term ‘eco‐evolutionary dynamics' as accessed on 7 January 2021. image

Inhibitory effects of climate change on the growth and extracellular enzyme activities of a widespread Antarctic soil fungus - Marta Misiak; William P. Goodall‐Copestake; Tim H. Sparks; M. Roger Worland; Lynne Boddy; Naresh Magan; Peter Convey; David W. Hopkins; Kevin K. Newsham (Global Change Biology, 2021)
Temperatures approaching or exceeding 20°C have been measured during summer in polar regions at the surfaces of barren fellfield soils under cloudless skies around solar noon. However, despite the upper temperature limit for the growth of cold‐adapted microbes—which are abundant in polar soils and have pivotal roles in nutrient cycling—typically being close to this temperature, previous studies have not addressed the consequences of climate change for the metabolism of these organisms in the natural environment. Here in a 5‐year field experiment on Alexander Island in the southern maritime Antarctic, we show that the abundance of Pseudogymnoascus roseus , the most widespread decomposer fungus in maritime Antarctic fellfield soils, is reduced by 1–2 orders of magnitude when irrigated and nutrient‐amended soils are warmed to >20°C during summer. Laboratory experiments under conditions mimicking those during midsummer in the natural environment indicated that the hyphal extension rates of P. roseus isolates and the activities of five extracellular enzymes are reduced by 54%–96% at high water availability after exposure to temperatures cycling daily from 2 to 21°C and 2 to 24°C, relative to temperatures cycling from 2 to 18°C. Given that the temperatures of surface soils at the study site already reach 19°C during midsummer, the observations reported here suggest that, at predicted rates of warming arising from moderate greenhouse gas emissions, inhibitory effects of climate change on the metabolism of P. roseus could manifest themselves within the next few decades. Furthermore, with peak temperatures at the surfaces of fellfield soils at other maritime Antarctic locations and in High Arctic and alpine regions already exceeding 20°C during summer, the observations suggest that climate warming has the potential to inhibit the growth of other cold‐adapted microbes, with negative effects on soils as the Earth's climate continues to warm.

A research perspective towards a more complete biodiversity footprint: a report from the World Biodiversity Forum - Alexandra Marques; Marine Robuchon; Stefanie Hellweg; Tim Newbold; Jutta Beher; Sebastian Bekker; Franz Essl; Daniele Ehrlich; Samantha Hill; Martin Jung; Sandra Marquardt; Francesca Rosa; et al. (The International Journal of Life Cycle Assessment, 2021)

Unlocking the phylogenetic diversity, primary habitats, and abundances of free‐living Symbiodiniaceae on a coral reef - Lisa Fujise; David J. Suggett; Michael Stat; Tim Kahlke; Michael Bunce; Stephanie G. Gardner; Samantha Goyen; Stephen Woodcock; Peter J. Ralph; Justin R. Seymour; Nachshon Siboni; Matthew R. Nitschke (Molecular Ecology, 2021)
Dinoflagellates of the family Symbiodiniaceae form mutualistic symbioses with marine invertebrates such as reef‐building corals, but also inhabit reef environments as free‐living cells. Most coral species acquire Symbiodiniaceae horizontally from the surrounding environment during the larval and/or recruitment phase, however the phylogenetic diversity and ecology of free‐living Symbiodiniaceae on coral reefs is largely unknown. We coupled environmental DNA sequencing and genus‐specific qPCR to resolve the community structure and cell abundances of free‐living Symbiodiniaceae in the water column, sediment, and macroalgae and compared these to coral symbionts. Sampling was conducted at two time points, one of which coincided with the annual coral spawning event when recombination between hosts and free‐living Symbiodiniaceae is assumed to be critical. Amplicons of the internal transcribed spacer (ITS2) region were assigned to 12 of the 15 Symbiodiniaceae genera or genera‐equivalent lineages. Community compositions were separated by habitat, with water samples containing a high proportion of sequences corresponding to coral symbionts of the genus Cladocopium , potentially as a result of cell expulsion from in hospite populations. Sediment‐associated Symbiodiniaceae communities were distinct, potentially due to the presence of exclusively free‐living species. Intriguingly, macroalgal surfaces displayed the highest cell abundances of Symbiodiniaceae, suggesting a key role for macroalgae in ensuring the ecological success of corals through maintenance of a continuum between environmental and symbiotic populations of Symbiodiniaceae.

Invasion costs, impacts, and human agency: response to Sagoff 2020 - Ross N. Cuthbert; Sven Bacher; Tim M. Blackburn; Elizabeta Briski; Christophe Diagne; Jaimie T. A. Dick; Franz Essl; Piero Genovesi; Phillip J. Haubrock; Guillaume Latombe; Bernd Lenzner; Yves Meinard; et al. (Conservation Biology, 2020)
Article impact statement : In an era of profound biodiversity crisis, invasion costs, invader impacts, and human agency should not be dismissed.

Predators, Disease, and Environmental Change in the Nearshore Ecosystem: Mortality in Southern Sea Otters (Enhydra lutris nereis) From 1998–2012 - Melissa A. Miller; Megan E. Moriarty; Laird Henkel; Martin Tim Tinker; Tristan L. Burgess; Francesca I. Batac; Erin Dodd; Colleen Young; Michael D. Harris; David A. Jessup; Jack Ames; Patricia A. Conrad; et al. (Frontiers in Marine Science, 2020)
We compiled findings from 15 years (1998–2012) of southern sea otter ( Enhydra lutris nereis ) necropsies, incorporating data from 560 animals. Sensitive diagnostic tests were used to detect biotoxins, bacteria, parasites and fungi. Methods to classify primary and contributing causes of death (COD) and sequelae utilized an updated understanding of health risks affecting this population. Several interesting patterns emerged, including identification of coastal regions of high mortality risk for sea otter mortality due to shark bite, cardiomyopathy, toxoplasmosis, sarcocystosis, acanthocephalan peritonitis and coccidioidomycosis. We identified demographic attributes that enhanced the risk of disease in relation to age, sex, and reproductive stage. Death due to white shark ( Carcharodon carcharias ) bite increased dramatically during the study period and was the most common primary COD. However, when primary and contributing COD were combined, the most prevalent COD was infectious disease (affecting 63% of otters), especially fatal infections by acanthocephalans ( Profilicollis spp.) and protozoa (e.g., Sarcocystis neurona and Toxoplasma gondii ). Fatal bacterial infections were also extremely common as a primary process or a sequela, affecting 68% of examined otters. Substantial advances were made in identifying sea otters that died following exposure to the pervasive marine neurotoxin domoic acid (DA), and DA intoxication was conservatively estimated as a primary or contributing COD for 20% of otters. Cardiomyopathy was also highly prevalent as a primary or contributing COD (41%) and exhibited significant associations with DA intoxication and protozoal infection. For adult and aged adult females in late pup care through post-weaning at the time of death, 83% had end lactation syndrome (ELS) as a primary or contributing COD. This comprehensive longitudinal dataset is unique in its depth and scope. The large sample size and extensive time period provided an opportunity to investigate mortality patterns in a changing environment and identify spatial and temporal disease “hot spots” and emerging threats. Our findings will help improve estimates of population-level impacts of specific threats and optimize conservation and environmental mitigation efforts for this threatened species.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Herbivore-induced volatile emissions are altered by soil legacy effects in cereal cropping systems - Shealyn C. Malone; David K. Weaver; Tim F. Seipel; Fabian D. Menalled; Megan L. Hofland; Justin B. Runyon; Amy M. Trowbridge (Plant and Soil, 2020)
Aims (main purpose and research question) Soil properties, including microbial composition and nutrient availability, can influence the emissions of plant volatile organic compounds (VOCs) that serve as host-location cues for insect pests and their natural enemies. Agricultural practices have profound effects on soil properties, but how these influence crop VOCs remains largely unknown. The aim of this study was to investigate the effect of agricultural practices on constitutive and herbivore-induced VOC emissions by a major staple crop through soil legacy effects. Methods In a full factorial experiment, we measured VOC emissions by wheat ( Triticum aestivum ) grown in soil inoculum from wheat-fallow or wheat-cover crop rotations that was subjected to feeding by larval Cephus cinctus . Results (main findings) Under herbivory, plants grown in cover crop inoculum emitted greater total VOCs, including higher concentrations of 2-pentadecanone, an insect repellent, and nonanal, a compound important in the recruitment of natural enemies. Plants grown in fallow inoculum showed no differences in emissions whether under herbivory or not. Soil inoculum did not influence VOC emissions of plants in the absence of larval feeding. Conclusions These results suggest that agricultural practices influence crop VOC emissions through soil legacy effects. Additionally, crops grown in wheat-fallow rotations may be less successful recruiting natural enemies of pests through herbivore-induced VOC signaling. Abbreviations Volatile organic compounds (VOCs); herbivore-induced plant volatiles (HIPV); green leaf volatiles (GLVs); northern Great Plains (NGP); wheat stem sawfly (WSS); gas chromatography-mass spectrometry (GC-MS); non-metric multidimensional scaling (NMDS); generalized linear mixed-effects model (GLMM).

Increasing picocyanobacteria success in shelf waters contributes to long‐term food web degradation - Katrin Schmidt; Antony J. Birchill; Angus Atkinson; Robert J. W. Brewin; James R. Clark; Anna E. Hickman; David G. Johns; Maeve C. Lohan; Angela Milne; Silvia Pardo; Luca Polimene; Tim J. Smyth; et al. (Global Change Biology, 2020)
Continental margins are disproportionally important for global primary production, fisheries and CO 2 uptake. However, across the Northeast Atlantic shelves, there has been an ongoing summertime decline of key biota—large diatoms, dinoflagellates and copepods—that traditionally fuel higher tropic levels such as fish, sea birds and marine mammals. Here, we combine multiple time series with in situ process studies to link these declines to summer nutrient stress and increasing proportions of picophytoplankton that can comprise up to 90% of the combined pico‐ and nanophytoplankton biomass in coastal areas. Among the pico‐fraction, it is the cyanobacterium Synechococcus that flourishes when iron and nitrogen resupply to surface waters are diminished. Our field data show how traits beyond small size give Synechococcus a competitive edge over pico‐ and nanoeukaryotes. Key is their ability to grow at low irradiances near the nutricline, which is aided by their superior light‐harvesting system and high affinity to iron. However, minute size and lack of essential biomolecules (e.g. omega‐3 polyunsaturated fatty acids and sterols) render Synechococcus poor primary producers to sustain shelf sea food webs efficiently. The combination of earlier spring blooms and lower summer food quantity and quality creates an increasing period of suboptimal feeding conditions for zooplankton at a time of year when their metabolic demand is highest. We suggest that this nutrition‐related mismatch has contributed to the widespread, ~50% decline in summer copepod abundance we observe over the last 60 years. With Synechococcus clades being prominent from the tropics to the Arctic and their abundances increasing worldwide, our study informs projections of future food web dynamics in coastal and shelf areas where droughts and stratification lead to increasing nutrient starvation of surface waters.

The COVID-19 pandemic: local to global implications as perceived by urban ecologists - Ian Douglas; Mark Champion; Joy Clancy; David Haley; Marcelo Lopes de Souza; Kerry Morrison; Alan Scott; Richard Scott; Miriam Stark; Joanne Tippett; Piotr Tryjanowski; Tim Webb (Socio-Ecological Practice Research, 2020)
The global COVID-19 pandemic is affecting everyone, but in many different ways, stimulating contrasting reactions and responses: opportunities for some, difficulties for many. A simple survey of how individual workers in urban ecology have been coping with COVID-19 constraints found divergent responses to COVID-19 on people’s activities, both within countries and between continents. Many academics felt frustrated at being unable to do fieldwork, but several saw opportunities to change ways of working and review their engagement with the natural world. Some engaging with social groups found new ways of sharing ideas and developing aspirations without face-to-face contact. Practitioners creating and managing urban greenspaces had to devise ways to work and travel while maintaining social distancing. Many feared severe funding impacts from changed local government priorities. Around the world, the COVID-19 pandemic has amplified issues, such as environmental injustice, disaster preparation and food security, that have been endemic in most countries across the global south in modern times. However, developing and sustaining the strong community spirit shown in many places will speed economic recovery and make cities more resilient against future geophysical and people-made disasters. Significantly, top-down responses and one-size-fits-all solutions, however good the modelling on which they are based, are unlikely to succeed without the insights that local knowledge and community understanding can bring. We all will have to look at disaster preparation in a more comprehensive, caring and consistent way in future.

Surface Inorganic Iodine Speciation in the Indian and Southern Oceans From 12°N to 70°S - Rosie Chance; Liselotte Tinel; Amit Sarkar; Alok K. Sinha; Anoop S. Mahajan; Racheal Chacko; P. Sabu; Rajdeep Roy; Tim D. Jickells; David P. Stevens; Martin Wadley; Lucy J. Carpenter (Frontiers in Marine Science, 2020)

A Cautionary Tale: Quantitative LC-HRMS Analytical Procedures for the Analysis of N-Nitrosodimethylamine in Metformin - Jingyue Yang; Tim Andres Marzan; Wei Ye; Cynthia D. Sommers; Jason D. Rodriguez; David A. Keire (The AAPS Journal, 2020)
A private testing laboratory reported in a Citizen Petition (CP) to FDA that 16 of 38 metformin drug products they tested had N -nitrosodimethyl amine (NDMA) amounts above the allowable intake (AI) of 96 ng/day. Because the FDA had been monitoring drugs for nitrosamines, orthogonal analytical procedures had been developed, validated and applied to detect the following nitrosamines in metformin drug products (if present): (i) NDMA (with a dedicated method) or (ii) NDMA (with a second confirmatory method), N -nitroso-diethylamine (NDEA), N -ethyl- N -nitroso-2-propanamine (NEIPA), N -nitroso-diisopropylamine (NDIPA), N -nitroso-di-n-propylamine (NDPA), N -nitroso-methylphenylamine (NMPA), N -nitroso-di-n-butylamine (NDBA) and N -nitroso- N -methyl-4-aminobutyric acid (NMBA). In contrast to the private laboratory results, FDA testing on the same set of 38 samples with orthogonal procedures observed amounts over the AI in only 8 of the 38 products and generally observed lower values than reported by the private testing laboratory. As described here, the investigation into the cause of the discrepancy revealed that N,N -dimethylformamide (DMF) can interfere with NDMA measurements. The data showed that the use of sufficient mass accuracy in the data acquisition and appropriate mass tolerance setting in the data processing to assure the selectivity of mass spectrometry measurements of NDMA in the presence of co-eluting DMF was necessary to prevent overestimation of the level of NDMA in metformin drug products. Overall, care should be taken to assure the necessary specificity in analytical procedures for adequate assessment of the nitrosamine level in drug products that also contain DMF or other potential interfering substances.

The EU-ToxRisk method documentation, data processing and chemical testing pipeline for the regulatory use of new approach methods - Alice Krebs; Barbara M. A. van Vugt-Lussenburg; Tanja Waldmann; Wiebke Albrecht; Jan Boei; Bas ter Braak; Maja Brajnik; Thomas Braunbeck; Tim Brecklinghaus; Francois Busquet; Andras Dinnyes; Joh Dokler; et al. (Archives of Toxicology, 2020)
Hazard assessment, based on new approach methods (NAM), requires the use of batteries of assays, where individual tests may be contributed by different laboratories. A unified strategy for such collaborative testing is presented. It details all procedures required to allow test information to be usable for integrated hazard assessment, strategic project decisions and/or for regulatory purposes. The EU-ToxRisk project developed a strategy to provide regulatorily valid data, and exemplified this using a panel of > 20 assays (with > 50 individual endpoints), each exposed to 19 well-known test compounds (e.g. rotenone, colchicine, mercury, paracetamol, rifampicine, paraquat, taxol). Examples of strategy implementation are provided for all aspects required to ensure data validity: (i) documentation of test methods in a publicly accessible database; (ii) deposition of standard operating procedures (SOP) at the European Union DB-ALM repository; (iii) test readiness scoring accoding to defined criteria; (iv) disclosure of the pipeline for data processing; (v) link of uncertainty measures and metadata to the data; (vi) definition of test chemicals, their handling and their behavior in test media; (vii) specification of the test purpose and overall evaluation plans. Moreover, data generation was exemplified by providing results from 25 reporter assays. A complete evaluation of the entire test battery will be described elsewhere. A major learning from the retrospective analysis of this large testing project was the need for thorough definitions of the above strategy aspects, ideally in form of a study pre-registration, to allow adequate interpretation of the data and to ensure overall scientific/toxicological validity.

Evidence for Rapoport’s rule and latitudinal patterns in the global distribution and diversity of alien bird species - Ellie E. Dyer; David W. Redding; Phillip Cassey; Ben Collen; Tim M. Blackburn (Journal of Biogeography, 2020)
Aim To quantify global latitudinal patterns in the distributions of alien bird species to assess whether these species conform to Rapoport's rule (i.e. show a positive latitudinal gradient in latitudinal range extent), and to test whether where species are introduced, and where species fail to establish, may help to drive observed patterns. Location Global. Taxon Birds (group Aves). Methods Data on locations of introduction and establishment for 355 species with established alien populations were combined with data on native range extents (measured in 5° bands of latitude). Relationships between (a) latitude and introduced and established alien species richness, and (b) latitude and introduced and established alien range extent, were plotted. Linear regressions and paired t ‐tests were used to compare latitudinal range extents, midpoints, and limits of each species in its introduced alien range, established alien range and native range. Results Latitudes that have more established alien bird species also have had more species introduced in total. The mean total latitudinal extents (i.e. geographic range size) of established alien bird species increase with latitude poleward of the tropics, consistent with Rapoport's rule, but are smaller in the tropics. This pattern is weaker in the range sizes of native bird species. Alien bird species are more likely to be introduced within the latitudinal confines of their native ranges, and are more likely to contract away from the more extreme latitudes to which they were introduced. Alien bird species are in general more likely to have established populations nearer the equator. Main conclusions Including data on locations of introduction in addition to established distributions enables us to determine the extent to which large‐scale alien species distributions are determined by anthropogenic or natural processes. Latitudinal patterns in range extent (Rapoport's rule) and species richness in alien birds are largely a consequence of where species have been introduced, and hence are unlikely to be informative of equivalent patterns in native species.

Environmental and Anthropogenic Factors Affect Fish Abundance: Relationships Revealed by Automated Cameras Deployed by Fishers - Michael A. Brooker; Simon de Lestang; David V. Fairclough; Dianne McLean; Dirk Slawinski; Matthew B. Pember; Tim J. Langlois (Frontiers in Marine Science, 2020)

Surfactin-producing Bacillus velezensis 1B-23 and Bacillus sp. 1D-12 protect tomato against bacterial canker caused by Clavibacter michiganensis subsp. michiganensis - Matthew Laird; David Piccoli; Brian Weselowski; Tim McDowell; Justin Renaud; Jacqueline MacDonald; Ze-Chun Yuan (Journal of Plant Pathology, 2020)

Symbiodiniaceae‐bacteria interactions: rethinking metabolite exchange in reef‐building corals as multi‐partner metabolic networks - Jennifer L. Matthews; Jean‐Baptiste Raina; Tim Kahlke; Justin R. Seymour; Madeleine J. H. van Oppen; David J. Suggett (Environmental Microbiology, 2020)
Summary The intimate relationship between scleractinian corals and their associated microorganisms is fundamental to healthy coral reef ecosystems. Coral‐associated microbes (Symbiodiniaceae and other protists, bacteria, archaea, fungi and viruses) support coral health and resilience through metabolite transfer, inter‐partner signalling, and genetic exchange. However, much of our understanding of the coral holobiont relationship has come from studies that have investigated either coral‐Symbiodiniaceae or coral‐bacteria interactions in isolation, while relatively little research has focused on other ecological and metabolic interactions potentially occurring within the coral multi‐partner symbiotic network. Recent evidences of intimate coupling between phytoplankton and bacteria have demonstrated that obligate resource exchange between partners fundamentally drives their ecological success. Here, we posit that similar associations with bacterial consortia regulate Symbiodiniaceae productivity and are in turn central to the health of corals. Indeed, we propose that this bacteria‐Symbiodiniaceae‐coral relationship underpins the coral holobiont's nutrition, stress tolerance and potentially influences the future survival of coral reef ecosystems under changing environmental conditions. Resolving Symbiodiniaceae‐bacteria associations is therefore a logical next step towards understanding the complex multi‐partner interactions occurring in the coral holobiont.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Revealing changes in the microbiome of Symbiodiniaceae under thermal stress - Emma F. Camp; Tim Kahlke; Matthew R. Nitschke; Deepa Varkey; Nerissa L. Fisher; Lisa Fujise; Samantha Goyen; David J. Hughes; Caitlin A. Lawson; Mickael Ros; Stephen Woodcock; Kun Xiao; et al. (Environmental Microbiology, 2020)
Summary Symbiodiniaceae are a diverse family of marine dinoflagellates, well known as coral endosymbionts. Isolation and in vitro culture of Symbiodiniaceae strains for physiological studies is a widely adopted tool, especially in the context of understanding how environmental stress perturbs Symbiodiniaceae cell functioning. While the bacterial microbiomes of corals often correlate with coral health, the bacterial communities co‐cultured with Symbiodiniaceae isolates have been largely overlooked, despite the potential of bacteria to significantly influence the emergent physiological properties of Symbiodiniaceae cultures. We examined the physiological response to heat stress by Symbiodiniaceae isolates (spanning three genera) with well‐described thermal tolerances, and combined these observations with matched changes in bacterial composition and abundance through 16S rRNA metabarcoding. Under thermal stress, there were Symbiodiniaceae strain‐specific changes in maximum quantum yield of photosystem II (proxy for health) and growth rates that were accompanied by changes in the relative abundance of multiple Symbiodiniaceae‐specific bacteria. However, there were no Symbiodiniaceae‐independent signatures of bacterial community reorganisation under heat stress. Notably, the thermally tolerant Durusdinium trenchii (ITS2 major profile D1a) had the most stable bacterial community under heat stress. Ultimately, this study highlights the complexity of Symbiodiniaceae‐bacteria interactions and provides a first step towards uncoupling their relative contributions towards Symbiodiniaceae physiological functioning.

Komodo dragons are not ecological analogs of apex mammalian predators - Tim S. Jessop; Achmad Ariefiandy; David M. Forsyth; Deni Purwandana; Craig R. White; Yunias Jackson Benu; Thomas Madsen; Henry J. Harlow; Mike Letnic (Ecology, 2020)
Apex predators can have substantial and complex ecological roles in ecosystems. However, differences in species‐specific traits, population densities, and interspecific interactions are likely to determine the strength of apex predators’ roles. Here we report complementary studies examining how interactions between predator per capita metabolic rate and population density influenced the biomass, population energy use, and ecological effects of apex predators on their large mammalian prey. We first investigated how large mammal prey resources and field metabolic rates of terrestrial apex predators, comprising large mammals and the Komodo dragon ( Varanus komodoensis ), influenced their biomass densities and population energy use requirements. We next evaluated whether Komodo dragons, like apex mammalian predators, exerted top‐down regulation of their large mammal prey. Comparison of results from field studies demonstrates that Komodo dragons attain mean population biomass densities that are 5.75−231.82 times higher than that of apex mammalian predator species and their guilds in Africa, Asia, and North America. The high biomass of Komodo dragons resulted in 1.96−108.12 times greater population energy use than that of apex mammalian predators. Nevertheless, substantial temporal and spatial variation in Komodo dragon population energy use did not regulate the population growth rates of either of two large mammal prey species, rusa deer ( Rusa timorensis ) and wild pig ( Sus scrofa ). We suggest that multiple processes weaken the capacity of Komodo dragons to regulate large mammal prey populations. For example, a low per capita metabolic rate requiring an infrequent and inactive hunting strategy (including scavenging), would minimize lethal and nonlethal impacts on prey populations. We conclude that Komodo dragons differ in their predatory role from, including not being the ecological analogs of, apex mammalian predators.

Historical reviews of the assessment of human cardiovascular function: interrogation and understanding of the control of skin blood flow - David. A. Low; Helen Jones; N. Tim Cable; Lacy M. Alexander; W. Larry Kenney (European Journal of Applied Physiology, 2020)
Several techniques exist for the determination of skin blood flow that have historically been used in the investigation of thermoregulatory control of skin blood flow, and more recently, in clinical assessments or as an index of global vascular function. Skin blood flow measurement techniques differ in their methodology and their strengths and limitations. To examine the historical development of techniques for assessing skin blood flow by describing the origin, basic principles, and important aspects of each procedure and to provide recommendations for best practise. Venous occlusion plethysmography was one of the earliest techniques to intermittently index a limb’s skin blood flow under conditions in which local muscle blood flow does not change. The introduction of laser Doppler flowmetry provided a method that continuously records an index of skin blood flow (red cell flux) (albeit from a relatively small skin area) that requires normalisation due to high site-to-site variability. The subsequent development of laser Doppler and laser speckle imaging techniques allows the mapping of skin blood flow from larger surface areas and the visualisation of capillary filling from the dermal plexus in two dimensions. The use of iontophoresis or intradermal microdialysis in conjunction with laser Doppler methods allows for the local delivery of pharmacological agents to interrogate the local and neural control of skin blood flow. The recent development of optical coherence tomography promises further advances in assessment of the skin circulation via three-dimensional imaging of the skin microvasculature for quantification of vessel diameter and vessel recruitment.

Making Lake Erie Smart by Driving Innovations in Technology and Networking - Becky Pearson; Tim Kearns; Tad Slawecki; Bryan Stubbs; Max Herzog; Kelli Paige; David Fitch (Frontiers in Marine Science, 2019)

Episodic memory for visual scenes suggests compensatory brain activity in breast cancer patients: a prospective longitudinal fMRI study - Denise Pergolizzi; James C. Root; Hong Pan; David Silbersweig; Emily Stern; Steven D. Passik; Tim A. Ahles (Brain Imaging and Behavior, 2019)

Variation in dissolved organic matter (DOM) stoichiometry in U.K. freshwaters: Assessing the influence of land cover and soil C:N ratio on DOM composition - Christopher A. Yates; Penny J. Johnes; Alun T. Owen; Francesca L. Brailsford; Helen C. Glanville; Christopher D. Evans; Miles R. Marshall; David L. Jones; Charlotte E. M. Lloyd; Tim Jickells; Richard P. Evershed (Limnology and Oceanography, 2019)
Dissolved organic matter (DOM) plays an important role in freshwater biogeochemistry. To investigate the influence of catchment character on the quality and quantity of DOM in freshwaters, 45 sampling sites draining subcatchments of contrasting soil type, hydrology, and land cover within one large upland‐dominated and one large lowland‐dominated catchment were sampled over a 1‐yr period. Dominant land cover in each subcatchment included: arable and horticultural, blanket peatland, coniferous woodland, and improved, unimproved, acid, and calcareous grasslands. The composition of the C, N, and P pool was determined as a function of the inorganic nutrient species (NO 3 − , NO 2 − , NH 4 + , and PO 4 3− ) and dissolved organic nutrient (dissolved organic carbon [DOC], dissolved organic nitrogen [DON], and dissolved organic phosphorus [DOP]) concentrations. DOM quality was assessed by calculation of the molar DOC : DON and DOC : DOP ratios and specific ultraviolet absorbance (SUVA 254 ). In catchments with little anthropogenic nutrient inputs, DON and DOP typically composed > 80% of the total dissolved nitrogen (TDN) and total dissolved phosphorus (TDP) concentrations. By contrast, in heavily impacted agricultural catchments DON and DOP typically comprised 5–15% of TDN and 10–25% of TDP concentrations. Significant differences in DOC : DON and DOC : DOP ratios were observed between land cover class with significant correlations observed between both the DOC : DON and DOC : DOP molar ratios and SUVA 254 ( r s = 0.88 and 0.84, respectively). Analysis also demonstrated a significant correlation between soil C : N ratio and instream DOC : DON/DOP ( r s = 0.79 and 0.71, respectively). We infer from this that soil properties, specifically the C : N ratio of the soil organic matter pool, has a significant influence on the composition of DOM in streams draining through these landscapes.

Validation of Tidal Stream Turbine Wake Predictions and Analysis of Wake Recovery Mechanism - Sanchit Salunkhe; Oumnia El Fajri; Shanti Bhushan; David Thompson; Daphne O’Doherty; Tim O’Doherty; Allan Mason-Jones (Journal of Marine Science and Engineering, 2019)
This paper documents the predictive capability of rotating blade-resolved unsteady Reynolds averaged Navier-Stokes (URANS) and Improved Delayed Detached Eddy Simulation (IDDES) computations for tidal stream turbine performance and intermediate wake characteristics. Ansys/Fluent and OpenFOAM simulations are performed using mixed-cell, unstructured grids consisting of up to 11 million cells. The thrust, power and intermediate wake predictions compare reasonably well within 10% of the experimental data. For the wake predictions, OpenFOAM performs better than Ansys/Fluent, and IDDES better than URANS when the resolved turbulence is triggered. The primary limitation of the simulations is under prediction of the wake diffusion towards the turbine axis, which in return is related to the prediction of turbulence in the tip-vortex shear layer. The shear-layer involves anisotropic turbulent structures; thus, hybrid RANS/LES models, such as IDDES, are preferred over URANS. Unfortunately, IDDES fails to accurately predict the resolved turbulence in the near-wake region due to the modeled stress depletion issue.

Normal modes and resonance in Ontario Lacus: a hydrocarbon lake of Titan - David Vincent; Jonathan Lambrechts; Özgür Karatekin; Tim Van Hoolst; Robert H. Tyler; Véronique Dehant; Eric Deleersnijder (Ocean Dynamics, 2019)

Does Lidocaine Cause False Positive Results on Cocaine Urine Drug Screen? - Eungjae Kim; Brian Patrick Murray; Maryam Salehi; Tim P. Moran; Joseph E. Carpenter; David D. Koch; James C. Ritchie; Joanna M. Schindler; Brent W. Morgan (Journal of Medical Toxicology, 2019)

Uncertainty in geomorphological responses to climate change - Stephan Harrison; Tim Mighall; David A. Stainforth; Philip Allen; Mark Macklin; Edward Anderson; Jasper Knight; Dmitri Mauquoy; David Passmore; Brice Rea; Matteo Spagnolo; Sarah Shannon (Climatic Change, 2019)

What We Have Learned From the Framework for Ocean Observing: Evolution of the Global Ocean Observing System - Toste Tanhua; Andrea McCurdy; Albert Fischer; Ward Appeltans; Nicholas Bax; Kim Currie; Brad DeYoung; Daniel Dunn; Emma Heslop; Linda K. Glover; John Gunn; Katherine Hill; et al. (Frontiers in Marine Science, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Ship-Based Contributions to Global Ocean, Weather, and Climate Observing Systems - Shawn R. Smith; Gaël Alory; Axel Andersson; William Asher; Alex Baker; David I. Berry; Kyla Drushka; Darin Figurskey; Eric Freeman; Paul Holthus; Tim Jickells; Henry Kleta; et al. (Frontiers in Marine Science, 2019)

Correction to: Mass coral bleaching of P. versipora in Sydney Harbour driven by the 2015–2016 heatwave - Samantha Goyen; Emma F. Camp; Lisa Fujise; Alicia Lloyd; Matthew R. Nitschke; Todd C. LaJeunesse; Tim Kahlke; Peter J. Ralph; David Suggett (Coral Reefs, 2019)

Mass coral bleaching of P. versipora in Sydney Harbour driven by the 2015–2016 heatwave - Samantha Goyen; Emma F. Camp; Lisa Fujise; Alicia Lloyd; Matthew R. Nitschke; Todd LaJeunensse; Tim Kahlke; Peter J. Ralph; David Suggett (Coral Reefs, 2019)

Waves and Swells in High Wind and Extreme Fetches, Measurements in the Southern Ocean - Alexander V. Babanin; W. Erick Rogers; Ricardo de Camargo; Martin Doble; Tom Durrant; Kirill Filchuk; Kevin Ewans; Mark Hemer; Tim Janssen; Boris Kelly-Gerreyn; Keith Machutchon; Peter McComb; et al. (Frontiers in Marine Science, 2019)

Ground Data are Essential for Biomass Remote Sensing Missions - Jérôme Chave; Stuart J. Davies; Oliver L. Phillips; Simon L. Lewis; Plinio Sist; Dmitry Schepaschenko; John Armston; Tim R. Baker; David Coomes; Mathias Disney; Laura Duncanson; Bruno Hérault; et al. (Surveys in Geophysics, 2019)

Breeding and wintering bird distributions in Britain and Ireland from citizen science bird atlases - Simon Gillings; Dawn E. Balmer; Brian J. Caffrey; Iain S. Downie; David W. Gibbons; Peter C. Lack; James B. Reid; J. Tim R. Sharrock; Robert L. Swann; Robert J. Fuller (Global Ecology and Biogeography, 2019)
Motivation We undertook large citizen science surveys of bird distributions (atlases) in Britain and Ireland, aimed at quantifying breeding bird distributions on a 20‐year cycle and wintering bird distributions on a c . 30‐year cycle. We use these to generate spatially referenced information on apparent changes in bird distributions over c . 40 years. Main type of variable contained Detection of breeding and wintering bird species in grid squares during five periods, and changes in detection between periods. The combined distribution dataset contains 1,410,938 records detailing detections of 465 bird species in 3,880 grid cells in different periods. The combined distribution change dataset contains 1,297,791 records describing stability, apparent colonization or apparent extinction of individual species in grid squares between pairs of atlases spanning up to c. 40 years. Spatial location and grain Grid squares (10 km × 10 km) containing land throughout Britain, Ireland, the Isle of Man and the Channel Islands. The majority of data are at 10‐km resolution, but data for rare species are summarized at 20‐ or 50‐km resolution to protect sensitive locations. Time period The data represent summarized detection information derived from fieldwork during five periods: the breeding seasons 1968–1972, 1988–1991 and 2008–2011, and the winters 1981/1982–1983/1984 and 2007/2008–2010/2011. Major taxa studied and level of measurement Birds; their distribution derived from citizen science surveys. Software format Data are supplied as comma‐separated text files.

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

A Global Ocean Observing System (GOOS), Delivered Through Enhanced Collaboration Across Regions, Communities, and New Technologies - Tim Moltmann; Jon Turton; Huai-Min Zhang; Glenn Nolan; Carl Gouldman; Laura Griesbauer; Zdenka Willis; Ángel Muñiz Piniella; Sue Barrell; Erik Andersson; Champika Gallage; Etienne Charpentier; et al. (Frontiers in Marine Science, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

A study on optimization of pat gene expression cassette for maize transformation - Elumalai Sivamani; Samson Nalapalli; Anna Prairie; David Bradley; Lee Richbourg; Tim Strebe; Tara Liebler; Daolong Wang; Qiudeng Que (Molecular Biology Reports, 2019)

Efficacy of Bordeaux mixture in reducing pecan scab in the southeastern USA - Clive H. Bock; Michael W. Hotchkiss; David I. Shapiro-Ilan; Lenny Wells; Jason Brock; Tim Brenneman; Russ Mizell (Organic Agriculture, 2019)

Chitinozoans and scolecodonts from the Silurian and Devonian of Japan - Thijs R. A. Vandenbroucke; Olle Hints; Mark Williams; Simon Wallis; Jules Velleman; Toshiyuki Kurihara; Gengo Tanaka; Toshifumi Komatsu; Peep Männik; David J. Siveter; Tim de Backer (Island Arc, 2019)
Silurian and Devonian chitinozoans and scolecodonts are recorded from strata of the Hida‐Gaien Terrane, central Honshu. Silurian chitinozoans include Eisenackitina , Bursachitina , and the species Angochitina elongata . The latter provides a precise biostratigraphical tie between the Japanese succession and the Type Ludlow Series of the Welsh Borderland, UK, and indicates a Ludlow age (Gorstian or early Ludfordian) for the upper member of the Yoshiki Formation in the Ichinotani Valley. Chitinozoans from other Yoshiki Formation localities contain other specimens of Lagenochitinidae. Scolecodonts are more common than chitinozoans in the palynological residues, but are mostly represented by fragments or minor apparatus elements with a low biostratigraphical value. However, material from the Yoshiki and Fukuji Formations includes several species of Mochtyella as well as representatives of Oenonites , Kettnerites , Lunoprionella , Vistulella ? and possibly other placognath taxa. Scolecodonts are also present in the Silurian Middle Member of the Gionyama Formation, Kyushu, including a well‐preserved jaw of Pistoprion , and fragments of putative Kettnerites and Oenonites . These finds of scolecodonts suggest close similarity in assemblages between Paleozoic polychaete faunas of Japanese terranes and those of Baltica‐Laurentia.

Power and phase coherence in sensorimotor mu and temporal lobe alpha components during covert and overt syllable production - Andrew Bowers; Tim Saltuklaroglu; David Jenson; Ashley Harkrider; David Thornton (Experimental Brain Research, 2019)

Combining multiple visual surveys to model the habitat of deep‐diving cetaceans at the basin scale - Auriane Virgili; Matthieu Authier; Oliver Boisseau; Ana Cañadas; Diane Claridge; Tim Cole; Peter Corkeron; Ghislain Dorémus; Léa David; Nathalie Di‐Méglio; Charlotte Dunn; Tim E. Dunn; et al. (Global Ecology and Biogeography, 2019)
Aim Deep‐diving cetaceans are oceanic species exposed to multiple anthropogenic pressures including high intensity underwater noise, and knowledge of their distribution is crucial to manage their conservation. Due to intrinsic low densities, wide distribution ranges and limited presence at the sea surface, these species are rarely sighted. Pooling data from multiple visual surveys sharing a common line‐transect methodology can increase sightings but requires accounting for heterogeneity in protocols and platforms. Location North Atlantic Ocean and Mediterranean Sea. Time period 1998 to 2015. Major taxa Ziphiidae; Physeteriidae; Kogiidae. Methods About 1,240,000 km of pooled effort provided 630 sightings of ziphiids, 836 of physeteriids and 106 of kogiids. For each taxon, we built a hierarchical model to estimate the effective strip width depending on observation conditions and survey types. We then modelled relative densities in a generalized additive modelling framework. Geographical predictions were limited to interpolations identified with a gap analysis of environmental space coverage. Results Deeper areas of the North Atlantic gyre were mostly environmental extrapolation in the predictions, thereby highlighting gaps in sampling across the different surveys. For the three species groups, the highest relative densities were predicted along continental slopes, particularly in the western North Atlantic Ocean where the Gulf Stream creates dynamic frontal zones and eddies. Main conclusions Pooling a large number of surveys provided the first basin‐wide models of distribution for deep‐diving cetaceans, including several data‐deficient taxa, across the North Atlantic Ocean and the Mediterranean Sea. These models can help the conservation of elusive and poorly known marine megafauna.

Developing a list of invasive alien species likely to threaten biodiversity and ecosystems in the European Union - Helen E. Roy; Sven Bacher; Franz Essl; Tim Adriaens; David C. Aldridge; John D. D. Bishop; Tim M. Blackburn; Etienne Branquart; Juliet Brodie; Carles Carboneras; Elizabeth J. Cottier-Cook; Gordon H. Copp; et al. (Global Change Biology, 2019)
The European Union ( EU ) has recently published its first list of invasive alien species ( IAS ) of EU concern to which current legislation must apply. The list comprises species known to pose great threats to biodiversity and needs to be maintained and updated. Horizon scanning is seen as critical to identify the most threatening potential IAS that do not yet occur in Europe to be subsequently risk assessed for future listing. Accordingly, we present a systematic consensus horizon scanning procedure to derive a ranked list of potential IAS likely to arrive, establish, spread and have an impact on biodiversity in the region over the next decade. The approach is unique in the continental scale examined, the breadth of taxonomic groups and environments considered, and the methods and data sources used. International experts were brought together to address five broad thematic groups of potential IAS . For each thematic group the experts first independently assembled lists of potential IAS not yet established in the EU but potentially threatening biodiversity if introduced. Experts were asked to score the species within their thematic group for their separate likelihoods of i) arrival, ii) establishment, iii) spread, and iv) magnitude of the potential negative impact on biodiversity within the EU . Experts then convened for a 2‐day workshop applying consensus methods to compile a ranked list of potential IAS . From an initial working list of 329 species, a list of 66 species not yet established in the EU that were considered to be very high (8 species), high (40 species) or medium (18 species) risk species was derived. Here, we present these species highlighting the potential negative impacts and the most likely biogeographic regions to be affected by these potential IAS.

Positive effects of the pollinators Osmia cornuta (Megachilidae) and Lucilia sericata (Calliphoridae) on strawberry quality - John David Herrmann; Henriette Beye; Christel de la Broise; Hollyn Hartlep; Tim Diekötter (Arthropod-Plant Interactions, 2019)

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Testicular Cancer on the Web—an Appropriate Source of Patient Information in Concordance with the European Association of Urology Guidelines? - Pia Paffenholz; Johannes Salem; Hendrik Borgmann; Tim Nestler; David Pfister; Christian Ruf; Igor Tsaur; Axel Haferkamp; Axel Heidenreich (Journal of Cancer Education, 2018)

Ten‐year assessment of the 100 priority questions for global biodiversity conservation - Tommaso Jucker; Bonnie Wintle; Gorm Shackelford; Pierre Bocquillon; Jan Laurens Geffert; Tim Kasoar; Eszter Kovacs; Hannah S. Mumby; Chloé Orland; Judith Schleicher; Eleanor R. Tew; Aiora Zabala; et al. (Conservation Biology, 2018)
In 2008, a group of conservation scientists compiled a list of 100 priority questions for the conservation of the world's biodiversity. However, now almost a decade later, no one has yet published a study gauging how much progress has been made in addressing these 100 high‐priority questions in the peer‐reviewed literature. We took a first step toward reexamining the 100 questions to identify key knowledge gaps that remain. Through a combination of a questionnaire and a literature review, we evaluated each question on the basis of 2 criteria: relevance and effort. We defined highly relevant questions as those that – if answered – would have the greatest impact on global biodiversity conservation and quantified effort based on the number of review publications addressing a particular question, which we used as a proxy for research effort. Using this approach, we identified a set of questions that, despite being perceived as highly relevant, have been the focus of relatively few review publications over the past 10 years. These questions covered a broad range of topics but predominantly tackled 3 major themes: conservation and management of freshwater ecosystems, role of societal structures in shaping interactions between people and the environment, and impacts of conservation interventions. We believe these questions represent important knowledge gaps that have received insufficient attention and may need to be prioritized in future research.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Seasonal variations in the availability of fodder resources and practices of dairy cattle feeding among the smallholder farmers in Western Usambara Highlands, Tanzania - David Maleko; Wai-Tim Ng; George Msalya; Angello Mwilawa; Liliane Pasape; Kelvin Mtei (Tropical Animal Health and Production, 2018)

Reliable low precision simulations in land surface models - Andrew Dawson; Peter D. Düben; David A. MacLeod; Tim N. Palmer (Climate Dynamics, 2018)

Revisiting an arid LGM using fluvial archives: a luminescence chronology for palaeochannels of the Murrumbidgee River, south‐eastern Australia - Daniela Mueller; Zenobia Jacobs; Tim J. Cohen; David M. Price; Ivars V. Reinfelds; James Shulmeister (Journal of Quaternary Science, 2018)
The Riverine Plain in south‐eastern Australia contains numerous palaeochannels that are much larger than the present rivers and provide evidence about past hydrological conditions. Previous research suggested optima in fluvial activity both before and after the peak of the Last Glacial Maximum (LGM; 21 ± 3 ka), and, in some cases, throughout the LGM. In this study, we revisit palaeochannel remnants of the Gum Creek and Yanco palaeochannel systems along the Murrumbidgee River, which drains the high‐elevation catchments of the Australian Alps in south‐eastern Australia. We date fluvial and aeolian sediments using single‐grain optically stimulated luminescence (OSL) and apply thermoluminescence (TL) dating to a subset of samples. We compare the OSL ages to new and previously published TL ages and investigate reasons for age discrepancies between these methods, possible effects of partial bleaching and other factors that may affect luminescence ages. We propose a new OSL‐based chronology for the Gum Creek and Yanco palaeochannel systems and assign periods of enhanced fluvial activity for the Tombullen and Yanco phases to 41–29 and 29–18 ka, respectively. Importantly, we infer that conditions of increased sediment and water discharge persisted for the Murrumbidgee River at the time of the LGM.

Blocking and its Response to Climate Change - Tim Woollings; David Barriopedro; John Methven; Seok-Woo Son; Olivia Martius; Ben Harvey; Jana Sillmann; Anthony R. Lupo; Sonia Seneviratne (Current Climate Change Reports, 2018)

Impact of nitrogen availability upon the electron requirement for carbon fixation in Australian coastal phytoplankton communities - David J. Hughes; Deepa Varkey; Martina A. Doblin; Tim Ingleton; Allison Mcinnes; Peter J. Ralph; Virginie van Dongen‐Vogels; David J. Suggett (Limnology and Oceanography, 2018)
Nitrogen (N) availability affects phytoplankton photosynthetic performance and regulates marine primary production (MPP) across the global coast and oceans. Bio‐optical tools including Fast Repetition Rate fluorometry (FRRf) are particularly well suited to examine MPP variability in coastal regions subjected to dynamic spatio‐temporal fluctuations in nutrient availability. FRRf determines photosynthesis as an electron transport rate through Photosystem II (ETR PSII ), requiring knowledge of an additional parameter, the electron requirement for carbon fixation ( K C ), to retrieve rates of CO 2 ‐fixation. K C strongly depends upon environmental conditions regulating photosynthesis, yet the importance of N‐availability to this parameter has not been examined. Here, we use nutrient bioassays to isolate how N (relative to other macronutrients P, Si) regulates K C of phytoplankton communities from the Australian coast during summer, when N‐availability is often highly variable. K C consistently responded to N‐amendment, exhibiting up to a threefold reduction and hence an apparent increase in the efficiency with which electrons were used to drive C‐fixation. However, the process driving this consistent reduction was dependent upon initial conditions. When diatoms dominated assemblages and N was undetectable (e.g., post bloom), K C decreased predominantly via a physiological adjustment of the existing community to N‐amendment. Conversely, for mixed assemblages, N‐addition achieved a similar reduction in K C through a change in community structure toward diatom domination. We generate new understanding and parameterization of K C that is particularly critical to advance how FRRf can be applied to examine C‐uptake throughout the global ocean where nitrogen availability is highly variable and thus frequently limits primary productivity.

Species invasions and the phylogenetic signal in geographical range size - Alex L. Pigot; Ellie E. Dyer; David W. Redding; Phillip Cassey; Gavin H. Thomas; Tim M. Blackburn (Global Ecology and Biogeography, 2018)
Aim Accelerating rates of anthropogenic introductions are leading to a dramatic restructuring of species distributions globally. However, the extent to which invasions alter the imprint of evolutionary history in species geographical ranges remains unclear. Here, we provide a global assessment of how the introduction, establishment and spread of alien species alters the phylogenetic signal in geographical range size using birds as a model system. Location Global. Time period Contemporaneous. Taxa Birds. Methods We compare the phylogenetic signal in alien range size with that of native distributions of species globally ( n = 9,993) and across different stages in the invasion pathway, from introduced ( n = 965) to established species ( n = 359). Using stochastic simulations, we test whether differences in phylogenetic signal arise from nonrandom patterns of species introduction, establishment or spread. Results Geographical range size in birds exhibits an intermediate phylogenetic signal, driven by the spatial clustering of closely related species. Nonrandom introductions, biased towards wide‐ranging species from particular clades and regions, produce an anomalously strong phylogenetic signal in the native range size of introduced species. In contrast, the phylogenetic signal in alien range size is substantially weaker than for native distributions. This weak phylogenetic signal cannot be explained by a lack of time for dispersal but is instead regulated by phylogenetic correlations across species in the location and number of introduction events. Main conclusions We demonstrate that the effects of anthropogenic introductions on the phylogenetic signal in range size vary across different stages in the invasion pathway. The process of transport and introduction amplifies the phylogenetic signal in the pool of potential invaders, whereas the subsequent pattern of spread decouples variation in alien range size from phylogenetic ancestry. Together, our findings suggest that evolutionary relatedness is likely to be a relatively weak predictor of the spread of invasive species.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Elevated CO 2 did not affect the hydrological balance of a mature native Eucalyptus woodland - Teresa E. Gimeno; Tim R. McVicar; Anthony P. O'Grady; David T. Tissue; David S. Ellsworth (Global Change Biology, 2018)
Elevated atmospheric CO 2 concentration (e C a ) might reduce forest water‐use, due to decreased transpiration, following partial stomatal closure, thus enhancing water‐use efficiency and productivity at low water availability. If evapotranspiration ( E t ) is reduced, it may subsequently increase soil water storage (Δ S ) or surface runoff ( R ) and drainage ( D g ), although these could be offset or even reversed by changes in vegetation structure, mainly increased leaf area index ( L ). To understand the effect of e C a in a water‐limited ecosystem, we tested whether 2 years of e C a (~40% increase) affected the hydrological partitioning in a mature water‐limited Eucalyptus woodland exposed to Free‐Air CO 2 Enrichment (FACE). This timeframe allowed us to evaluate whether physiological effects of e C a reduced stand water‐use irrespective of L , which was unaffected by e C a in this timeframe. We hypothesized that e C a would reduce tree‐canopy transpiration ( E tree ), but excess water from reduced E tree would be lost via increased soil evaporation and understory transpiration ( E floor ) with no increase in Δ S , R or D g . We computed E t , Δ S , R and D g from measurements of sapflow velocity, L , soil water content (θ), understory micrometeorology, throughfall and stemflow. We found that e C a did not affect E tree , E floor , Δ S or θ at any depth (to 4.5 m) over the experimental period. We closed the water balance for dry seasons with no differences in the partitioning to R and D g between C a levels. Soil temperature and θ were the main drivers of E floor while vapour pressure deficit‐controlled E tree , though e C a did not significantly affect any of these relationships. Our results suggest that in the short‐term, e C a does not significantly affect ecosystem water‐use at this site. We conclude that water‐savings under e C a mediated by either direct effects on plant transpiration or by indirect effects via changes in L or soil moisture availability are unlikely in water‐limited mature eucalypt woodlands.

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

Genetic distinctiveness of brown pelicans (Pelecanus occidentalis) from the Galápagos Islands compared to continental North America - Scott A. Taylor; Melissa Jenkins; Meera Manghani; Tim Birt; David J. Anderson; Gustavo Jiménez-Uzcátegui; Vicki Friesen (Conservation Genetics, 2018)

Dietary plasticity in a nutrient-rich system does not influence brown bear (Ursus arctos) body condition or denning - Lindsey S. Mangipane; Jerrold L. Belant; Diana J. R. Lafferty; David D. Gustine; Tim L. Hiller; Michael E. Colvin; Buck A. Mangipane; Grant V. Hilderbrand (Polar Biology, 2018)

Multifarious anchovy and sardine regimes in the Humboldt Current System during the last 150 years - Renato Salvatteci; David Field; Dimitri Gutiérrez; Tim Baumgartner; Vicente Ferreira; Luc Ortlieb; Abdel Sifeddine; Daniel Grados; Arnaud Bertrand (Global Change Biology, 2018)
The Humboldt Current System ( HCS ) has the highest production of forage fish in the world, although it is highly variable and the future of the primary component, anchovy, is uncertain in the context of global warming. Paradigms based on late 20th century observations suggest that large‐scale forcing controls decadal‐scale fluctuations of anchovy and sardine across different boundary currents of the Pacific. We develop records of anchovy and sardine fluctuations since 1860 AD using fish scales from multiple sites containing laminated sediments and compare them with Pacific basin‐scale and regional indices of ocean climate variability. Our records reveal two main anchovy and sardine phases with a timescale that is not consistent with previously proposed periodicities. Rather, the regime shifts in the HCS are related to 3D habitat changes driven by changes in upwelling intensity from both regional and large‐scale forcing. Moreover, we show that a long‐term increase in coastal upwelling translates via a bottom‐up mechanism to top predators suggesting that the warming climate, at least up to the start of the 21st century, was favorable for fishery productivity in the HCS .

The role of astrocytic calcium and TRPV4 channels in neurovascular coupling - Allanah Kenny; Michael J. Plank; Tim David (Journal of Computational Neuroscience, 2018)

Assessing the impact of stocking northern-origin hatchery brook trout on the genetics of wild populations in North Carolina - David C. Kazyak; Jacob Rash; Barbara A. Lubinski; Tim L. King (Conservation Genetics, 2018)

iDNA at Sea: Recovery of Whale Shark (Rhincodon typus) Mitochondrial DNA Sequences from the Whale Shark Copepod (Pandarus rhincodonicus) Confirms Global Population Structure - Mark Meekan; Christopher M. Austin; Mun H. Tan; Nu-Wei V. Wei; Adam Miller; Simon J. Pierce; David Rowat; Guy Stevens; Tim K. Davies; Alessandro Ponzo; Han Ming Gan (Frontiers in Marine Science, 2017)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

Steric sea level variability (1993–2010) in an ensemble of ocean reanalyses and objective analyses - Andrea Storto; Simona Masina; Magdalena Balmaseda; Stéphanie Guinehut; Yan Xue; Tanguy Szekely; Ichiro Fukumori; Gael Forget; You-Soon Chang; Simon A. Good; Armin Köhl; Guillaume Vernieres; et al. (Climate Dynamics, 2017)

Assessing mid-latitude dynamics in extreme event attribution systems - Daniel Mitchell; Paolo Davini; Ben Harvey; Neil Massey; Karsten Haustein; Tim Woollings; Richard Jones; Fredi Otto; Benoit Guillod; Sarah Sparrow; David Wallom; Myles Allen (Climate Dynamics, 2017)

Blueprints of Effective Biodiversity and Conservation Knowledge Products That Support Marine Policy - Lauren V. Weatherdon; Ward Appeltans; Nadine Bowles-Newark; Thomas M. Brooks; Frances E. Davis; Katherine Despot-Belmonte; Stephen Fletcher; Cristina Garilao; Craig Hilton-Taylor; Tim Hirsch; Diego Juffe-Bignoli; Kristin Kaschner; et al. (Frontiers in Marine Science, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

An assessment of ectomycorrhizal fungal communities in Tasmanian temperate high-altitude Eucalyptus delegatensis forest reveals a dominance of the Cortinariaceae - Bryony M. Horton; Morag Glen; Neil J. Davidson; David A. Ratkowsky; Dugald C. Close; Tim J. Wardlaw; Caroline Mohammed (Mycorrhiza, 2017)

Climate regulation, energy provisioning and water purification: Quantifying ecosystem service delivery of bioenergy willow grown on riparian buffer zones using life cycle assessment - David Styles; Pål Börjesson; Tina D’Hertefeldt; Klaus Birkhofer; Jens Dauber; Paul Adams; Sopan Patil; Tim Pagella; Lars B. Pettersson; Philip Peck; Céline Vaneeckhaute; Håkan Rosenqvist (Ambio, 2016)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Integrating geoscience into undergraduate education about environment, society, and sustainability using place-based learning: three examples - David Gosselin; Steven Burian; Tim Lutz; Julie Maxson (Journal of Environmental Studies and Sciences, 2016)

A spatially explicit estimate of the prewhaling abundance of the endangered North Atlantic right whale - Sophie Monsarrat; M. Grazia Pennino; Tim D. Smith; Randall R. Reeves; Christine N. Meynard; David M. Kaplan; Ana S.L. Rodrigues (Conservation Biology, 2016)
The North Atlantic right whale (NARW) (Eubalaena glacialis) is one of the world's most threatened whales. It came close to extinction after nearly a millennium of exploitation and currently persists as a population of only approximately 500 individuals. Setting appropriate conservation targets for this species requires an understanding of its historical population size, as a baseline for measuring levels of depletion and progress toward recovery. This is made difficult by the scarcity of records over this species’ long whaling history. We sought to estimate the preexploitation population size of the North Atlantic right whale and understand how this species was distributed across its range. We used a spatially explicit data set on historical catches of North Pacific right whales (NPRWs) (Eubalaena japonica) to model the relationship between right whale relative density and the environment during the summer feeding season. Assuming the 2 right whale species select similar environments, we projected this model to the North Atlantic to predict how the relative abundance of NARWs varied across their range. We calibrated these relative abundances with estimates of the NPRW total prewhaling population size to obtain high and low estimates for the overall NARW population size prior to exploitation. The model predicted 9,075–21,328 right whales in the North Atlantic. The current NARW population is thus

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Developing a Snowmelt Forecast Model in the Absence of Field Data - Eric A. Sproles; Tim Kerr; Cristian Orrego Nelson; David Lopez Aspe (Water Resources Management, 2016)

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

Preserved emotional awareness of pain in a patient with extensive bilateral damage to the insula, anterior cingulate, and amygdala - Justin S. Feinstein; Sahib S. Khalsa; Tim V. Salomons; Kenneth M. Prkachin; Laura A. Frey-Law; Jennifer E. Lee; Daniel Tranel; David Rudrauf (Brain Structure and Function, 2016)

Temporal and interspecific variation in rates of spread for insect species invading Europe during the last 200 years - Alain Roques; Marie-Anne Auger-Rozenberg; Tim M. Blackburn; Jeff Garnas; Petr Pyšek; Wolfgang Rabitsch; David M. Richardson; Michael J. Wingfield; Andrew M. Liebhold; Richard P. Duncan (Biological Invasions, 2016)

The effects of asymmetric competition on the life history of Trinidadian guppies - Ronald D. Bassar; Dylan Z. Childs; Mark Rees; Shripad Tuljapurkar; David N. Reznick; Tim Coulson (Ecology Letters, 2016)
The effects of asymmetric interactions on population dynamics has been widely investigated, but there has been little work aimed at understanding how life history parameters like generation time, life expectancy and the variance in lifetime reproductive success are impacted by different types of competition. We develop a new framework for incorporating trait‐mediated density‐dependence into size‐structured models and use Trinidadian guppies to show how different types of competitive interactions impact life history parameters. Our results show the degree of symmetry in competitive interactions can have dramatic effects on the speed of the life history. For some vital rates, shifting the competitive superiority from small to large individuals resulted in a doubling of the generation time. Such large influences of competitive symmetry on the timescale of demographic processes, and hence evolution, highlights the interwoven nature of ecological and evolutionary processes and the importance of density‐dependence in understanding eco‐evolutionary dynamics.

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Sedimentary development and correlation of Late Quaternary terraces in the Kyrenia Range, northern Cyprus, using a combination of sedimentology and optical luminescence data - Romesh N. Palamakumbura; Alastair H. F. Robertson; Tim C. Kinnaird; David C. W. Sanderson (International Journal of Earth Sciences, 2016)

Trans-national horizon scanning for invasive non-native species: a case study in western Europe - Belinda Gallardo; Alexandra Zieritz; Tim Adriaens; Céline Bellard; Pieter Boets; J. Robert Britton; Jonathan R. Newman; Johan L. C. H. van Valkenburg; David C. Aldridge (Biological Invasions, 2016)

Best practice BioBanking of human heart tissue - Sean Lal; Amy Li; David Allen; Paul D. Allen; Paul Bannon; Tim Cartmill; Roger Cooke; Alan Farnsworth; Anne Keogh; Cristobal dos Remedios (Biophysical Reviews, 2015)

QTLs for Biomass and Developmental Traits in Switchgrass (Panicum virgatum) - David B. Lowry; Samuel H. Taylor; Jason Bonnette; Michael J. Aspinwall; Ashley L. Asmus; Tim H. Keitt; Christian M. Tobias; Thomas E. Juenger (BioEnergy Research, 2015)

Size-assortative mating in simultaneous hermaphrodites: an experimental test and a meta-analysis - Stuart Graham; Elodie Chapuis; Stefania Meconcelli; Nicolas Bonel; Kevin Sartori; Ananda Christophe; Pilar Alda; Patrice David; Tim Janicke (Behavioral Ecology and Sociobiology, 2015)

First recorded eruption of Nabro volcano, Eritrea, 2011 - Berhe Goitom; Clive Oppenheimer; James O. S. Hammond; Raphaël Grandin; Talfan Barnie; Amy Donovan; Ghebrebrhan Ogubazghi; Ermias Yohannes; Goitom Kibrom; J- Michael Kendall; Simon A. Carn; David Fee; et al. (Bulletin of Volcanology, 2015)

Diet is the primary determinant of bacterial community structure in the guts of higher termites - Aram Mikaelyan; Carsten Dietrich; Tim Köhler; Michael Poulsen; David Sillam‐Dussès; Andreas Brune (Molecular Ecology, 2015)
The gut microbiota of termites plays critical roles in the symbiotic digestion of lignocellulose. While phylogenetically ‘lower termites’ are characterized by a unique association with cellulolytic flagellates, higher termites (family Termitidae) harbour exclusively prokaryotic communities in their dilated hindguts. Unlike the more primitive termite families, which primarily feed on wood, they have adapted to a variety of lignocellulosic food sources in different stages of humification, ranging from sound wood to soil organic matter. In this study, we comparatively analysed representatives of different taxonomic lineages and feeding groups of higher termites to identify the major drivers of bacterial community structure in the termite gut, using amplicon libraries of 16S r RNA genes from 18 species of higher termites. In all analyses, the wood‐feeding species were clearly separated from humus and soil feeders, irrespective of their taxonomic affiliation, offering compelling evidence that diet is the primary determinant of bacterial community structure. Within each diet group, however, gut communities of termites from the same subfamily were more similar than those of distantly related species. A highly resolved classification using a curated reference database revealed only few genus‐level taxa whose distribution patterns indicated specificity for certain host lineages, limiting any possible cospeciation between the gut microbiota and host to short evolutionary timescales. Rather, the observed patterns in the host‐specific distribution of the bacterial lineages in termite guts are best explained by diet‐related differences in the availability of microhabitats and functional niches.

High-resolution skim genotyping by sequencing reveals the distribution of crossovers and gene conversions in Cicer arietinum and Brassica napus - Philipp E. Bayer; Pradeep Ruperao; Annaliese S. Mason; Jiri Stiller; Chon-Kit Kenneth Chan; Satomi Hayashi; Yan Long; Jinling Meng; Tim Sutton; Paul Visendi; Rajeev K. Varshney; Jacqueline Batley; et al. (Theoretical and Applied Genetics, 2015)

A Deep, Non-potable Water Supply for the Ochoa Sulphate of Potash (SOP) Mine Project, New Mexico, USA - Peter Castiglia; William Linderfelt; Cheng Cheng; Annelia Tinklenberg; David Jordan; Tim Dale; Randy Foote; Terre Lane (Mine Water and the Environment, 2015)

Delaying discharge after the stimulus significantly decreases muscle activation thresholds with small impact on the selectivity: an in vivo study using TIME - Paweł Maciejasz; Jordi Badia; Tim Boretius; David Andreu; Thomas Stieglitz; Winnie Jensen; Xavier Navarro; David Guiraud (Medical & Biological Engineering & Computing, 2015)

Genome edited sheep and cattle - Chris Proudfoot; Daniel F. Carlson; Rachel Huddart; Charles R. Long; Jane H. Pryor; Tim J. King; Simon G. Lillico; Alan J. Mileham; David G. McLaren; C. Bruce A. Whitelaw; Scott C. Fahrenkrug (Transgenic Research, 2015)

De novo mutations in beta-catenin (CTNNB1) appear to be a frequent cause of intellectual disability: expanding the mutational and clinical spectrum - Alma Kuechler; Marjolein H. Willemsen; Beate Albrecht; Carlos A. Bacino; Dennis W. Bartholomew; Hans van Bokhoven; Marie Jose H. van den Boogaard; Nuria Bramswig; Christian Büttner; Kirsten Cremer; Johanna Christina Czeschik; Hartmut Engels; et al. (Human Genetics, 2015)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Defining the Impact of Non‐Native Species - JONATHAN M. JESCHKE; SVEN BACHER; TIM M. BLACKBURN; JAIMIE T. A. DICK; FRANZ ESSL; THOMAS EVANS; MIRIJAM GAERTNER; PHILIP E. HULME; INGOLF KÜHN; AGATA MRUGAŁA; JAN PERGL; PETR PYŠEK; et al. (Conservation Biology, 2014)
Non‐native species cause changes in the ecosystems to which they are introduced. These changes, or some of them, are usually termed impacts; they can be manifold and potentially damaging to ecosystems and biodiversity. However, the impacts of most non‐native species are poorly understood, and a synthesis of available information is being hindered because authors often do not clearly define impact. We argue that explicitly defining the impact of non‐native species will promote progress toward a better understanding of the implications of changes to biodiversity and ecosystems caused by non‐native species; help disentangle which aspects of scientific debates about non‐native species are due to disparate definitions and which represent true scientific discord; and improve communication between scientists from different research disciplines and between scientists, managers, and policy makers. For these reasons and based on examples from the literature, we devised seven key questions that fall into 4 categories: directionality, classification and measurement, ecological or socio‐economic changes, and scale. These questions should help in formulating clear and practical definitions of impact to suit specific scientific, stakeholder, or legislative contexts. Definiendo el Impacto de las Especies No‐Nativas

Persistence and stability of Eastern Afromontane forests: evidence from brevicipitid frogs - Simon P. Loader; F. Sara Ceccarelli; Michele Menegon; Kim M. Howell; Roman Kassahun; Abebe A. Mengistu; Samy A. Saber; Fikirte Gebresenbet; Rafael de Sá; Tim R. B. Davenport; Joanna G. Larson; Hendrik Müller; et al. (Journal of Biogeography, 2014)
Aim The persistence and stability of habitats through time are considered predictors of high levels of biodiversity in some environments. Long‐term habitat persistence and stability may explain the species‐rich, endemic forest fauna and flora of the Eastern Afromontane Biodiversity Region ( EABR ). Using complementary phylogenetic and biogeographical approaches, we examine evolutionary patterns in EABR brevicipitid frogs. Using these data, we test whether brevicipitid history reflects patterns of long‐term forest persistence and/or stability across the EABR . Location East Africa. Methods A dated phylogeny for brevicipitids was constructed using two nuclear and three mitochondrial markers. Alternative diversification models were used to determine signal for constant or varying net diversification rates. Using our dated tree, we identified areas of high phylogenetic diversity ( PD ), and inferred ancestral areas using likelihood and Bayesian approaches. Results Brevicipitids have a long history, with generic diversification among extant lineages pre‐dating the Oligocene (> 33 Ma). Ancestral‐area reconstructions indicate the presence of brevicipitids in the EABR since the Oligocene, and support a scenario of palaeoendemics surviving in EABR refugia. Ancestral‐area reconstructions indicate that the central Eastern Arc Mountains ( EAM ) formed the initial centre of diversification of forest brevicipitids. Measures of PD show that diversity varies across the EABR but is highest in the EAM . Constant net diversification rate in brevicipitids is a significantly better fit than alternative, rate‐variable models. Main conclusions The degree of persistence of forest habitats appears to be a contributing factor to the varying levels of diversity across the EABR in brevicipitids (and other organisms). In contrast to the Southern Highlands and Ethiopian Bale Mountains, the EAM stands out as an area that enabled the constant accumulation of brevicipitid species over a long period of time.

Global mismatch between species richness and vulnerability of reef fish assemblages - Valeriano Parravicini; Sébastien Villéger; Tim R. McClanahan; Jesus Ernesto Arias‐González; David R. Bellwood; Jonathan Belmaker; Pascale Chabanet; Sergio R. Floeter; Alan M. Friedlander; François Guilhaumon; Laurent Vigliola; Michel Kulbicki; et al. (Ecology Letters, 2014)
The impact of anthropogenic activity on ecosystems has highlighted the need to move beyond the biogeographical delineation of species richness patterns to understanding the vulnerability of species assemblages, including the functional components that are linked to the processes they support. We developed a decision theory framework to quantitatively assess the global taxonomic and functional vulnerability of fish assemblages on tropical reefs using a combination of sensitivity to species loss, exposure to threats and extent of protection. Fish assemblages with high taxonomic and functional sensitivity are often exposed to threats but are largely missed by the global network of marine protected areas. We found that areas of high species richness spatially mismatch areas of high taxonomic and functional vulnerability. Nevertheless, there is strong spatial match between taxonomic and functional vulnerabilities suggesting a potential win–win conservation‐ecosystem service strategy if more protection is set in these locations.

The Agrodiversity Experiment: three years of data from a multisite study in intensively managed grasslands - Laura Kirwan; John Connolly; Caroline Brophy; Ole Baadshaug; Gilles Belanger; Alistair Black; Tim Carnus; Rosemary Collins; Jure Čop; Ignacio Delgado; Alex De Vliegher; Anjo Elgersma; et al. (Ecology, 2014)
Intensively managed grasslands are globally prominent ecosystems. We investigated whether experimental increases in plant diversity in intensively managed grassland communities can increase their resource use efficiency. This work consisted of a coordinated, continental‐scale 33‐site experiment. The core design was 30 plots, representing 15 grassland communities at two seeding densities. The 15 communities comprised four monocultures (two grasses and two legumes) and 11 four‐species mixtures that varied in the relative abundance of the four species at sowing. There were 1028 plots in the core experiment, with another 572 plots sown for additional treatments. Sites followed a protocol and employed the same experimental methods with certain plot management factors, such as seeding rates and number of cuts, determined by local practice. The four species used at a site depended on geographical location, but the species were chosen according to four functional traits: a fast‐establishing grass, a slow‐establishing persistent grass, a fast‐establishing legume, and a slow‐establishing persistent legume. As the objective was to maximize yield for intensive grassland production, the species chosen were all high‐yielding agronomic species. The data set contains species‐specific biomass measurements (yield per species and of weeds) for all harvests for up to four years at 33 sites. Samples of harvested vegetation were also analyzed for forage quality at 26 sites. These data should be of interest to ecologists studying relationships between diversity and ecosystem function and to agronomists interested in sustainable intensification. The large spatial scale of the sites provides opportunity for analyses across spatial (and temporal) scales. The database can also complement existing databases and meta‐analyses on biodiversity–ecosystem function relationships in natural communities by focusing on those same relationships within intensively managed agricultural grasslands.

Chronic cannabidiol treatment improves social and object recognition in double transgenic APPswe/PS1∆E9 mice - David Cheng; Jac Kee Low; Warren Logge; Brett Garner; Tim Karl (Psychopharmacology, 2014)

Adverse effects from antidepressant treatment: randomised controlled trial of 601 depressed individuals - Andrew A. Crawford; Sarah Lewis; David Nutt; Tim J. Peters; Philip Cowen; Michael C. O’Donovan; Nicola Wiles; Glyn Lewis (Psychopharmacology, 2014)

Closed-Loop Brain–Machine–Body Interfaces for Noninvasive Rehabilitation of Movement Disorders - Frédéric D. Broccard; Tim Mullen; Yu Mike Chi; David Peterson; John R. Iversen; Mike Arnold; Kenneth Kreutz-Delgado; Tzyy-Ping Jung; Scott Makeig; Howard Poizner; Terrence Sejnowski; Gert Cauwenberghs (Annals of Biomedical Engineering, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Measurement of Subvisible Particulates in Lyophilised Erwinia chrysanthemi l-asparaginase and Relationship with Clinical Experience - David Gervais; Tim Corn; Andrew Downer; Stuart Smith; Alan Jennings (The AAPS Journal, 2014)

A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands - Merritt R. Turetsky; Agnieszka Kotowska; Jill Bubier; Nancy B. Dise; Patrick Crill; Ed R. C. Hornibrook; Kari Minkkinen; Tim R. Moore; Isla H. Myers‐Smith; Hannu Nykänen; David Olefeldt; Janne Rinne; et al. (Global Change Biology, 2014)
Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to temperate), and disturbance. Fen methane flux was more sensitive to vegetation and less sensitive to temperature than bog or swamp fluxes. The optimal water table for methane flux was consistently below the peat surface in bogs, close to the peat surface in poor fens, and above the peat surface in rich fens. However, the largest flux in bogs occurred when dry 30‐day averaged antecedent conditions were followed by wet conditions, while in fens and swamps, the largest flux occurred when both 30‐day averaged antecedent and current conditions were wet. Drained wetlands exhibited distinct characteristics, e.g. the absence of large flux following wet and warm conditions, suggesting that the same functional relationships between methane flux and environmental conditions cannot be used across pristine and disturbed wetlands. Together, our results suggest that water table and temperature are dominant controls on methane flux in pristine bogs and swamps, while other processes, such as vascular transport in pristine fens, have the potential to partially override the effect of these controls in other wetland types. Because wetland types vary in methane emissions and have distinct controls, these ecosystems need to be considered separately to yield reliable estimates of global wetland methane release.

LIPAEMIC Report: Results of Clinical Use of Intravenous Lipid Emulsion in Drug Toxicity Reported to an Online Lipid Registry - Grant Cave; Martyn Harvey; Johann Willers; David Uncles; Tim Meek; John Picard; Guy Weinberg (Journal of Medical Toxicology, 2014)

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Human papillomavirus (HPV) 16 and the prognosis of head and neck cancer in a geographical region with a low prevalence of HPV infection - Rossana Verónica Mendoza López; José Eduardo Levi; José Eluf-Neto; Rosalina Jorge Koifman; Sergio Koifman; Maria Paula Curado; Pedro Michaluart-Junior; David Livingstone Alves Figueiredo; Fabiano Pinto Saggioro; Marcos Brasilino de Carvalho; Luiz Paulo Kowalski; Márcio Abrahão; et al. (Cancer Causes & Control, 2014)

SoilTrEC: a global initiative on critical zone research and integration - Manoj Menon; Svetla Rousseva; Nikolaos P. Nikolaidis; Pauline van Gaans; Panos Panagos; Danielle Maia de Souza; Kristin Vala Ragnarsdottir; Georg J. Lair; Liping Weng; Jaap Bloem; Pavel Kram; Martin Novak; et al. (Environmental Science and Pollution Research, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Modelling the ancient maize agriculture potential of landforms in Tikal National Park, Guatemala - Chris S. Balzotti; David L. Webster; Tim M. Murtha; Steven L. Petersen; Richard L. Burnett; Richard E. Terry (International Journal of Remote Sensing, 2013)

The performance of the global protected area system in capturing vertebrate geographic ranges - Lisette Cantú-Salazar; C. David L. Orme; Pamela C. Rasmussen; Tim M. Blackburn; Kevin J. Gaston (Biodiversity and Conservation, 2013)

Occupancy modelling as a new approach to assess supranational trends using opportunistic data: a pilot study for the damselfly Calopteryx splendens - Arco J. van Strien; Tim Termaat; Vincent Kalkman; Marijn Prins; Geert De Knijf; Anne-Laure Gourmand; Xavier Houard; Brian Nelson; Calijn Plate; Stephen Prentice; Eugenie Regan; David Smallshire; et al. (Biodiversity and Conservation, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Seasonal variation in ejaculate traits of male red-winged blackbirds (Agelaius phoeniceus) - Stefan Lüpold; Tim R. Birkhead; David F. Westneat (Behavioral Ecology and Sociobiology, 2012)

Consequences of change and variability in sea ice on marine ecosystem and biogeochemical processes during the 2007–2008 Canadian International Polar Year program - David G. Barber; Matthew G. Asplin; Tim N. Papakyriakou; Lisa Miller; Brent G. T. Else; John Iacozza; C. J. Mundy; M. Gosslin; Natalie C. Asselin; Steve Ferguson; Jennifer V. Lukovich; Gary A. Stern; et al. (Climatic Change, 2012)

Acidity controls on dissolved organic carbon mobility in organic soils - Chris D. Evans; Tim G. Jones; Annette Burden; Nick Ostle; Piotr Zieliński; Mark D. A. Cooper; Mike Peacock; Joanna M. Clark; Filip Oulehle; David Cooper; Chris Freeman (Global Change Biology, 2012)
Dissolved organic carbon ( DOC ) concentrations in surface waters have increased across much of E urope and N orth A merica, with implications for the terrestrial carbon balance, aquatic ecosystem functioning, water treatment costs and human health. Over the past decade, many hypotheses have been put forward to explain this phenomenon, from changing climate and land management to eutrophication and acid deposition. Resolution of this debate has been hindered by a reliance on correlative analyses of time series data, and a lack of robust experimental testing of proposed mechanisms. In a 4 year, four‐site replicated field experiment involving both acidifying and deacidifying treatments, we tested the hypothesis that DOC leaching was previously suppressed by high levels of soil acidity in peat and organo‐mineral soils, and therefore that observed DOC increases a consequence of decreasing soil acidity. We observed a consistent, positive relationship between DOC and acidity change at all sites. Responses were described by similar hyperbolic relationships between standardized changes in DOC and hydrogen ion concentrations at all sites, suggesting potentially general applicability. These relationships explained a substantial proportion of observed changes in peak DOC concentrations in nearby monitoring streams, and application to a UK ‐wide upland soil p H dataset suggests that recovery from acidification alone could have led to soil solution DOC increases in the range 46–126% by habitat type since 1978. Our findings raise the possibility that changing soil acidity may have wider impacts on ecosystem carbon balances. Decreasing sulphur deposition may be accelerating terrestrial carbon loss, and returning surface waters to a natural, high‐ DOC condition.

Observations on the entomopathogenic fungus Hirsutella citriformis attacking adult Diaphorina citri (Hemiptera: Psyllidae) in a managed citrus grove - David G. Hall; Matthew G. Hentz; Jason M. Meyer; Alissa B. Kriss; Tim R. Gottwald; Drion G. Boucias (BioControl, 2012)

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

C5a Receptor (CD88) Inhibition Improves Hypothermia-Induced Neuroprotection in an In Vitro Ischemic Model - John Thundyil; Dale Pavlovski; Yu-Hsuan Hsieh; Mathias Gelderblom; Tim Magnus; David P. Fairlie; Thiruma V. Arumugam (NeuroMolecular Medicine, 2012)

Myosin heavy chain mRNA isoforms are expressed in two distinct cohorts during C2C12 myogenesis - David M. Brown; Tim Parr; John M. Brameld (Journal of Muscle Research and Cell Motility, 2012)

Seasonal and interannual variation of the phytoplankton and copepod dynamics in Liverpool Bay - Naomi Greenwood; Rodney M. Forster; Veronique Créach; Suzanne J. Painting; Anna Dennis; Stewart J. Cutchey; Tiago Silva; David B. Sivyer; Tim Jickells (Ocean Dynamics, 2012)

Characteristics of two distinct high-light acclimated algal communities during advanced stages of sea ice melt - C. J. Mundy; Michel Gosselin; Jens K. Ehn; Claude Belzile; Michel Poulin; Eva Alou; Suzanne Roy; Haakon Hop; Sylvie Lessard; Tim N. Papakyriakou; David G. Barber; Jeremy Stewart (Polar Biology, 2011)

Effects of altitude exposure on brain natriuretic peptide in humans - David Woods; Tim Hooper; Pete Hodkinson; Steve Ball; Rob Wakeford; Bob Peaston; Claire Bairsto; Nic Green; Adrian Mellor (European Journal of Applied Physiology, 2011)

Shallow degassing events as a trigger for very-long-period seismicity at Kīlauea Volcano, Hawai‘i - Matthew Patrick; David Wilson; David Fee; Tim Orr; Don Swanson (Bulletin of Volcanology, 2011)

Impacts of the ‘Pacific Adventurer’ Oil Spill on the Macrobenthos of Subtropical Sandy Beaches - Thomas Alfred Schlacher; Andrew Holzheimer; Tim Stevens; David Rissik (Estuaries and Coasts, 2011)

Cyclic spattering, seismic tremor, and surface fluctuation within a perched lava channel, Kīlauea Volcano - Matthew R. Patrick; Tim Orr; David Wilson; David Dow; Richard Freeman (Bulletin of Volcanology, 2011)

A reassessment of late glacial – Holocene diatom oxygen isotope record from Lake Baikal using a geochemical mass‐balance approach - Anson W. Mackay; George E. A. Swann; Tim S. Brewer; Melanie J. Leng; David W. Morley; Natalia Piotrowska; Patrick Rioual; Dustin White (Journal of Quaternary Science, 2011)
We present a new palaeoenvironmental record of hydrological variability in Lake Baikal, based on re‐modelled δ 18 O diatom values of diatom silica (δ 18 O modelled ), where the residual contaminants are identified and compensated for using electron optical imaging and whole‐sample geochemistry. δ 18 O modelled interpretations are based on the balance between rivers with high δ 18 O values and rivers with low δ 18 O values. Isotopic variability is related to latitudinal differences in precipitation which feed these rivers. The δ 18 O modelled record suggests that rather moist conditions prevailed in the Lake Baikal region during the latter stages of the Younger Dryas. Throughout the Holocene, episodes of low δ 18 O modelled values are, in general, in good agreement with increases in percentage haematite‐stained grains in North Atlantic sediments (indicative of ice‐rafted debris events). Rivers with southerly catchments dominate fluvial input especially between c . 3.3 and 2 cal ka BP, concurrent with high precipitation in the Lake Baikal region. Copyright © 2011 John Wiley & Sons, Ltd.

Neurologic manifestations of human immunodeficiency virus-2: dementia, myelopathy, and neuropathy in West Africa - Youngjee Choi; John Townend; Tim Vincent; Irfan Zaidi; Ramu Sarge-Njie; Assan Jaye; David B. Clifford (Journal of NeuroVirology, 2011)

Geographical variation in sperm morphology in the red-winged blackbird (Agelaius phoeniceus) - Stefan Lüpold; David F. Westneat; Tim R. Birkhead (Evolutionary Ecology, 2011)

Distribution of soil carbon and microbial biomass in arable soils under different tillage regimes - Benhua Sun; Paul D. Hallett; Sandra Caul; Tim J. Daniell; David W. Hopkins (Plant and Soil, 2011)

Turnover and trends in butterfly communities on two British tidal islands: stochastic influences and deterministic factors - Roger L. H. Dennis; Leonardo Dapporto; Tim H. Sparks; Steven R. Williams; J. Nick Greatorex‐Davies; Jim Asher; David B. Roy (Journal of Biogeography, 2010)
Aim Community trends were investigated for two small islands and two local mainland butterfly communities within the UK over a period of 20–30 years. Location Hilbre Island off the Wirral Peninsula at 53.33° N, 3.10° W; Lindisfarne, an island off the Northumberland coast at 56.41° N, 1.48° W; Leighton Moss at 54.08° N, 2.26° W; Wyre Forest at 52.23° N, 2.14° W, UK. Methods Butterfly species data were collected on Hilbre and two mainland sites (Leighton Moss and Wyre Forest) from 1983 to 2006, and on Lindisfarne from 1977 to 2006, as part of the National Habitat Survey, the UK Butterfly Monitoring Scheme and ‘Butterflies for the New Millennium Atlas’ recording. Matrices of associations (Sokal and Michener’s matching coefficient S SM ; resemblance coefficient) were computed between years and subject to non‐metric multidimensional scaling (NMDS) and Mantel tests. The pattern of extinctions and colonizations at sites were examined, their heterogeneity tested by applying a Friedman test to fractional incidences for the same years. Regression analysis (multiple regression and logit regression) was used to relate butterfly numbers and incidences to climate variables, time and previous records. Results Significant community trends based on population counts and species’ incidences were found for all four sites. There was a significant climatic signal for Hilbre; although this was not apparent for the remaining sites, significant associations occurred between records for a number of species and climatic variables at all sites. Substantial turnover of species on the islands was inversely related to numbers of records for species but not to their conspicuousness to recorders. Main conclusions We argue that time trends are widespread in butterfly communities, even for relatively short periods; they are largely generated by stochastic influences rather than by more substantive factors such as climate change. Potential biases in surveying and recording history are shown to be unlikely. A clear climate signal was found only for the small Hilbre Island, for which there was also evidence for the significant influence of colonization capability of individual source species. We conclude that for many species, small islands will be sinks or pseudosinks and their ‘populations’ vulnerable to small changes in source–sink dynamics.

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Integrating the Totality of Food and Nutrition Evidence for Public Health Decision Making and Communication - Juan L. Navia; Tim Byers; Darinka Djordjevic; Eric Hentges; Janet King; David Klurfeld; Craig Llewellyn; John Milner; Daniel Skrypec; Douglas Weed (Critical Reviews in Food Science and Nutrition, 2010)

The many roles of vision during walking - David Logan; Tim Kiemel; Nadia Dominici; Germana Cappellini; Yuri Ivanenko; Francesco Lacquaniti; John J. Jeka (Experimental Brain Research, 2010)

Long-Term Trends in Submersed Aquatic Vegetation (SAV) in Chesapeake Bay, USA, Related to Water Quality - Robert J. Orth; Michael R. Williams; Scott R. Marion; David J. Wilcox; Tim J. B. Carruthers; Kenneth A. Moore; W. Michael Kemp; William C. Dennison; Nancy Rybicki; Peter Bergstrom; Richard A. Batiuk (Estuaries and Coasts, 2010)

Storm track sensitivity to sea surface temperature resolution in a regional atmosphere model - Tim Woollings; Brian Hoskins; Mike Blackburn; David Hassell; Kevin Hodges (Climate Dynamics, 2010)

The effect of 48 weeks of aerobic exercise training on cutaneous vasodilator function in post-menopausal females - Gary J. Hodges; Lisa Sharp; Claire Stephenson; Ashish Y. Patwala; Keith P. George; David F. Goldspink; N. Tim Cable (European Journal of Applied Physiology, 2010)

ATP Transport in Saccular Cerebral Aneurysms at Arterial Bends - Yohsuke Imai; Kodai Sato; Takuji Ishikawa; Andrew Comerford; Tim David; Takami Yamaguchi (Annals of Biomedical Engineering, 2010)

Evidence of increased electro-mechanical delay in the left and right ventricle after prolonged exercise - Fang Chan-Dewar; David Oxborough; Rob Shave; Warren Gregson; Greg Whyte; Tim Noakes; Keith George (European Journal of Applied Physiology, 2010)

Anatomy of a low temperature zircon outgrowth - Duncan C. Hay; Tim J. Dempster; Martin R. Lee; David J. Brown (Contributions to Mineralogy and Petrology, 2010)

Proteinases involved in matrix turnover during cartilage and bone breakdown - Tim E. Cawston; David A. Young (Cell and Tissue Research, 2010)

Successive Holocene rock avalanches at Lake Coleridge, Canterbury, New Zealand - Jenny Lee; Tim Davies; David Bell (Landslides, 2009)

Estimating the annual number of breeding attempts from breeding dates using mixture models - Thomas Cornulier; David A. Elston; Peter Arcese; Tim G. Benton; David J.T. Douglas; Xavier Lambin; Jane Reid; Robert A. Robinson; William J. Sutherland (Ecology Letters, 2009)
Well‐established statistical methods exist to estimate variation in a number of key demographic rates from field data, including life‐history transition probabilities and reproductive success per attempt. However, our understanding of the processes underlying population change remains incomplete without knowing the number of reproductive attempts individuals make annually; this is a key demographic rate for which we have no satisfactory method of estimating. Using census data to estimate this parameter from requires disaggregating the overlying temporal distributions of first and subsequent breeding attempts. We describe a Bayesian mixture method to estimate the annual number of reproductive attempts from field data to provide a new tool for demographic inference. We validate our method using comprehensive data on individually‐marked song sparrows Melospiza melodia , and then apply it to more typical nest record data collected over 45 years on yellowhammers Emberiza citrinella . We illustrate the utility of our method by testing, and rejecting, the hypothesis that declines in UK yellowhammer populations have occurred concurrently with declines in annual breeding frequency.

Mortality in adult intensive care patients with severe systemic inflammatory response syndromes is strongly associated with the hypo-immune TNF −238A polymorphism - John V. Pappachan; Tim G. Coulson; Nicholas J. A. Child; David J. Markham; Sarah M. Nour; Mark C. K. Pulletz; Matthew J. Rose-Zerilli; Kim de Courcey-Golder; Sheila J. Barton; Ian A. Yang; John W. Holloway (Immunogenetics, 2009)

Contrasting evolution of diversity at two disease-associated chicken genes - Tim Downing; David J. Lynn; Sarah Connell; Andrew T. Lloyd; A. K. Fazlul Haque Bhuiyan; Pradeepa Silva; Arifa N. Naqvi; Rahamame Sanfo; Racine-Samba Sow; Baitsi Podisi; Cliona O’Farrelly; Olivier Hanotte; et al. (Immunogenetics, 2009)

Contrasting evolution of diversity at two disease-associated chicken genes - Tim Downing; David J. Lynn; Sarah Connell; Andrew T. Lloyd; AK Fazlul Haque Bhuiyan; Pradeepa Silva; Arifa N. Naqvi; Rahamame Sanfo; Racine-Samba Sow; Baitsi Podisi; Cliona O’Farrelly; Olivier Hanotte; et al. (Immunogenetics, 2009)

Global biogeography and ecology of body size in birds - Valérie A. Olson; Richard G. Davies; C. David L. Orme; Gavin H. Thomas; Shai Meiri; Tim M. Blackburn; Kevin J. Gaston; Ian P. F. Owens; Peter M. Bennett (Ecology Letters, 2009)
In 1847, Karl Bergmann proposed that temperature gradients are the key to understanding geographic variation in the body sizes of warm‐blooded animals. Yet both the geographic patterns of body‐size variation and their underlying mechanisms remain controversial. Here, we conduct the first assemblage‐level global examination of ‘Bergmann’s rule’ within an entire animal class. We generate global maps of avian body size and demonstrate a general pattern of larger body sizes at high latitudes, conforming to Bergmann’s rule. We also show, however, that median body size within assemblages is systematically large on islands and small in species‐rich areas. Similarly, while spatial models show that temperature is the single strongest environmental correlate of body size, there are secondary correlations with resource availability and a strong pattern of decreasing body size with increasing species richness. Finally, our results suggest that geographic patterns of body size are caused both by adaptation within lineages, as invoked by Bergmann, and by taxonomic turnover among lineages. Taken together, these results indicate that while Bergmann’s prediction based on physiological scaling is remarkably accurate, it is far from the full picture. Global patterns of body size in avian assemblages are driven by interactions between the physiological demands of the environment, resource availability, species richness and taxonomic turnover among lineages.

Production of Dissolved Organic Carbon in Canadian Forest Soils - Tim R. Moore; David Paré; Robert Boutin (Ecosystems, 2008)

Fine-mapping the genetic basis of CRP regulation in African Americans: a Bayesian approach - Benjamin Rhodes; David L. Morris; Lakshman Subrahmanyan; Cristin Aubin; Carlos F. Mendes de Leon; Jeremiah F. Kelly; Dennis A. Evans; John C. Whittaker; Jorge R. Oksenberg; Philip L. De Jager; Tim J. Vyse (Human Genetics, 2008)

Computer Model of Nucleotide Transport in a Realistic Porcine Aortic Trifurcation - Andrew Comerford; Tim David (Annals of Biomedical Engineering, 2008)

Regional variation in the historical components of global avian species richness - Gavin H. Thomas; C. David L. Orme; Richard G. Davies; Valerie A. Olson; Peter M. Bennett; Kevin J. Gaston; Ian P. F. Owens; Tim M. Blackburn (Global Ecology and Biogeography, 2008)
Aim Using a global data base of the distribution of extant bird species, we examine the evidence for spatial variation in the evolutionary origins of contemporary avian diversity. In particular, we assess the possible role of the timing of mountain uplift in promoting diversification in different regions. Location Global. Methods We mapped the distribution of avian richness at four taxonomic levels on an equal‐area 1° grid. We examined the relationships between richness at successive taxonomic levels (e.g. species richness vs. genus richness). We mapped the residuals from linear regressions of these relationships to identify areas that are exceptional in the number of lower taxa relative to the number of higher taxa. We use generalized least squares models to test the influence of elevation range and temperature on lower‐taxon richness relative to higher‐taxon richness. Results Peaks of species richness in the Neotropics were congruent with patterns of generic richness, whilst peaks in Australia and the Himalayas were congruent with patterns of both genus and family richness. Hotspots in the Afrotropics did not reflect higher‐taxon patterns. Regional differences in the relationship between richness at successive taxonomic levels revealed variation in patterns of taxon co‐occurrence. Species and genus co‐occurrence was positively associated with elevational range across much of the world. Taxon occurrence in the Neotropics was associated with a positive interaction between elevational range and temperature. Conclusions These results demonstrate that contemporary patterns of richness show different associations with higher‐taxon richness in different regions, which implies that the timing of historical effects on these contemporary patterns varies across regions. We suggest that this is due to dispersal limitation and phylogenetic constraints on physiological tolerance limits promoting diversification. We speculate that diversification rates respond to long‐term changes in the Earth's topography, and that the role of tropical mountain ranges is implicated as a correlate of contemporary diversity, and a source of diversification across avian evolutionary history.

Mechanisms for the land/sea warming contrast exhibited by simulations of climate change - Manoj M. Joshi; Jonathan M. Gregory; Mark J. Webb; David M. H. Sexton; Tim C. Johns (Climate Dynamics, 2008)

Effects of acute tyrosine/phenylalanine depletion on the selective processing of smoking-related cues and the relative value of cigarettes in smokers - Brian Hitsman; James MacKillop; Anne Lingford-Hughes; Tim M. Williams; Faheem Ahmad; Sally Adams; David J. Nutt; Marcus R. Munafò (Psychopharmacology, 2008)

Dispersal of large branchiopod cysts: potential movement by wind from potholes on the Colorado Plateau - Tim B. Graham; David Wirth (Hydrobiologia, 2008)

Toll-like receptor 7 is not necessary for retroviral neuropathogenesis but does contribute to virus-induced neuroinflammation - Stephanie D Lewis; Niranjan B Butchi; Mohammed Khaleduzzaman; Tim W Morgan; Min Du; Susan Pourciau; David G. Baker; Shizuo Akira; Karin E. Peterson (Journal of NeuroVirology, 2008)

Environmental predictors of global parrot (Aves: Psittaciformes) species richness and phylogenetic diversity - Richard G. Davies; C. David L. Orme; Andrea J. Webster; Kate E. Jones; Tim M. Blackburn; Kevin J. Gaston (Global Ecology and Biogeography, 2007)
Aim Spatial patterns of phylogenetic diversity (PD) aid our ability to discern diversification rate mechanisms underlying hypotheses for the large‐scale distribution of biodiversity. We develop a predictive framework for the way in which spatial patterns of PD vary with those of species richness, depending on the balance between speciation and extinction rates. Within this framework, diversification processes thought to underlie the productive energy, ambient energy, topographic variability and habitat variety hypotheses predict that gradients of increase in species richness will be associated with: (1) decreasing extinction rates where driven by productive energy, hence increasing relative PD (i.e. PD controlling for species richness, or PD rel ); (2) a similar positive relationship between ambient energy and PD rel ; (3) increasing speciation rates where driven by topographic variability, hence decreasing PD rel ; and (4) no consistent relationship between PD rel and habitat variety when driven by the latter. We test these predictions using distributional data on parrots. Location Neotropical, Afrotropical, Indo‐Malayan and Australasian realms. Methods Spatial models were used to test the predictions. Results Globally, a positive association between productive energy and PD rel confirms prediction (1). However, within realms, hump‐shaped relationships suggest the importance of decreasing extinction rates up to a threshold level of productive energy, and the increasing importance of speciation rates thereafter. Ambient energy is positively associated with PD rel in Australasia, Indo‐Malaya, and globally, supporting prediction (2). However, this is driven by the coincidence of highest PD rel in areas of high ambient energy and intermediate productive energy (i.e. in seasonal tropical environments), which may be characterized by relatively low speciation and extinction rates. In the Neotropics, increasing topographic variability is associated with decreasing PD rel and increasing species richness, suggesting an increasing gradient of speciation, supporting prediction (3). Elsewhere, the signal of this mechanism may be obscured by collinearities with energy gradients. The lack of an overall relationship between habitat diversity and PD rel confirms prediction (4). Main conclusions Spatial patterns of PD rel in relation to environmental gradients may be sensitive to collinearities among those gradients. Nevertheless, patterns emerge which have implications for the relative importance of speciation and extinction processes in generating latitudinal diversity gradients.

Development and assessment of a coupled crop–climate model - TOM M. OSBORNE; DAVID M LAWRENCE; ANDREW J. CHALLINOR; JULIA M. SLINGO; TIM R. WHEELER (Global Change Biology, 2007)
It is well established that crop production is inherently vulnerable to variations in the weather and climate. More recently the influence of vegetation on the state of the atmosphere has been recognized. The seasonal growth of crops can influence the atmosphere and have local impacts on the weather, which in turn affects the rate of seasonal crop growth and development. Considering the coupled nature of the crop–climate system, and the fact that a significant proportion of land is devoted to the cultivation of crops, important interactions may be missed when studying crops and the climate system in isolation, particularly in the context of land use and climate change. To represent the two‐way interactions between seasonal crop growth and atmospheric variability, we integrate a crop model developed specifically to operate at large spatial scales (General Large Area Model for annual crops) into the land surface component of a global climate model (GCM; HadAM3). In the new coupled crop–climate model, the simulated environment (atmosphere and soil states) influences growth and development of the crop, while simultaneously the temporal variations in crop leaf area and height across its growing season alter the characteristics of the land surface that are important determinants of surface fluxes of heat and moisture, as well as other aspects of the land‐surface hydrological cycle. The coupled model realistically simulates the seasonal growth of a summer annual crop in response to the GCM's simulated weather and climate. The model also reproduces the observed relationship between seasonal rainfall and crop yield. The integration of a large‐scale single crop model into a GCM, as described here, represents a first step towards the development of fully coupled crop and climate models. Future development priorities and challenges related to coupling crop and climate models are discussed.

Energy, range dynamics and global species richness patterns: reconciling mid‐domain effects and environmental determinants of avian diversity - David Storch; Richard G. Davies; Samuel Zajíček; C. David L. Orme; Valerie Olson; Gavin H. Thomas; Tzung‐Su Ding; Pamela C. Rasmussen; Robert S. Ridgely; Peter M. Bennett; Tim M. Blackburn; Ian P. F. Owens; et al. (Ecology Letters, 2006)
Spatial patterns of species richness follow climatic and environmental variation, but could reflect random dynamics of species ranges (the mid‐domain effect, MDE). Using data on the global distribution of birds, we compared predictions based on energy availability (actual evapotranspiration, AET, the best single correlate of avian richness) with those of range dynamics models. MDE operating within the global terrestrial area provides a poor prediction of richness variation, but if it operates separately within traditional biogeographic realms, it explains more global variation in richness than AET. The best predictions, however, are given by a model of global range dynamics modulated by AET, such that the probability of a range spreading into an area is proportional to its AET. This model also accurately predicts the latitudinal variation in species richness and variation of species richness both within and between realms, thus representing a compelling mechanism for the major trends in global biodiversity.

Ten years of bacterial genome sequencing: comparative-genomics-based discoveries - Tim T. Binnewies; Yair Motro; Peter F. Hallin; Ole Lund; David Dunn; Tom La; David J. Hampson; Matthew Bellgard; Trudy M. Wassenaar; David W. Ussery (Functional & Integrative Genomics, 2006)

The FeL model of iron acquisition: Nondissociative reduction of ferric complexes in the marine environment - Tim P. Salmon; Andrew L. Rose; Brett A. Neilan; T. David Waite (Limnology and Oceanography, 2006)
Recently there has been recognition of the importance of reductive processes in the acquisition of iron by microorganisms in marine environments with Fe(III) reduction induced by either membrane‐bound reductases or by superoxide, a powerful Fe(III) reducing agent generated either by photochemical or biological means. We have measured the relative rates of iron uptake achieved by the cyanobacterium L. majuscula in the presence of a variety of model‐ and naturally‐derived organic ligands exhibiting a broad range of conditional ferric and ferrous stability constants. Additionally, we have investigated the effect upon iron uptake rate of varying the concentration of both iron and the iron‐binding ligands. We have reconciled this data with previous work in which we measured rates of reduction by exogenous superoxide of Fe(III) bound to these same complexes. We show that the rate of formation of ferrous iron and the rate of uptake of iron by Lyngbya majuscul a are each independent of the concentration of Fe' and demonstrate that this is consistent with our previous finding that this organism acquires iron via nondissociative reduction of ferric complexes. We also show that the rate of reoxidation of organically complexed Fe(II) is a critical determinant of the subsequent bioavailability of iron, a feature not previously addressed in the literature. In view of the central importance of the complexation and redox behavior of the iron‐ organic complexes to iron uptake rate, we propose a new kinetic model of iron acquisition, termed the FeL model, that is consistent with presented and previously published data and which describes processes both in natural and artificial conditions.

The TNFα receptor TNFRSF1A and genes encoding the amiloride-sensitive sodium channel ENaC as modulators in cystic fibrosis - Frauke Stanke; Tim Becker; Harry Cuppens; Vinod Kumar; Jean-Jacques Cassiman; Silke Jansen; Dragica Radojkovic; Benny Siebert; Jennifer Yarden; David W. Ussery; Thomas F. Wienker; Burkhard Tümmler (Human Genetics, 2006)

Effects of Arterial Bifurcation Geometry on Nucleotide Concentration at the Endothelium - Andrew Comerford; Tim David; Mike Plank (Annals of Biomedical Engineering, 2006)

Phylogeographic Analyses Suggest Multiple Lineages of Crystallaria asprella (Percidae: Etheostominae) - Cheryl L. Morrison; David P. Lemarié; Robert M. Wood; Tim L. King (Conservation Genetics, 2006)

Global and local control of microtubule destabilization promoted by a catastrophe kinesin MCAK/XKCM1 - Kazuhisa Kinoshita; Tim L. Noetzel; Isabelle Arnal; David N. Drechsel; Anthony A. Hyman (Journal of Muscle Research and Cell Motility, 2006)

Model-based development of gemcabene, a new lipid-altering agent - Jaap W. Mandema; David Hermann; Wenping Wang; Tim Sheiner; Mark Milad; Rebecca Bakker-Arkema; Daniel Hartman (The AAPS Journal, 2005)

Does diet breadth control herbivorous insect distribution size? Life history and resource outlets for specialist butterflies - Roger L. H. Dennis; Tim G. Shreeve; Henry R. Arnold; David B. Roy (Journal of Insect Conservation, 2005)

Review of the Methods Frequently Used to Estimate the Abundance of Orthoptera in Grassland Ecosystems - Tim Gardiner; Julian Hill; David Chesmore (Journal of Insect Conservation, 2005)

The prevalence of non-indigenous species in southern California embayments and their effects on benthic macroinvertebrate communities - J. Ananda. Ranasinghe; Tim K. Mikel; Ronald G. Velarde; Stephen B. Weisberg; David E. Montagne; Donald B. Cadien; Ann Dalkey (Biological Invasions, 2005)

A global view of CK2 function and regulation - Allison Poole; Tim Poore; Sricharan Bandhakavi; Richard O. McCann; David E. Hanna; Claiborne V. C. Glover (Molecular and Cellular Biochemistry, 2005)

Parallel influence of climate on the behaviour of Pacific killer whales and Atlantic bottlenose dolphins - David Lusseau; Rob Williams; Ben Wilson; Kate Grellier; Tim R. Barton; Philip S. Hammond; Paul M. Thompson (Ecology Letters, 2004)
The grouping behaviour of animals is governed by intrinsic and extrinsic factors which play an important role in shaping their social organization. We investigated the influence of ocean climate variation on the grouping behaviour of two widely separated populations of cetaceans, inhabiting north Atlantic and north Pacific coastal waters. The group size of both bottlenose dolphins in the Moray Firth, UK, and killer whales in Johnstone Strait, Canada, varied from year to year in relation to large‐scale ocean climate variation. Local indices of prey abundance were also related both to climate indices and predator group sizes. The cetaceans tended to live in smaller groups when there was less salmon available in both areas which seem to occur 2 years after a lower phase of the North Atlantic and Pacific Decadal Oscillations. These findings suggest that, even in highly social mammals, climate variation may influence social organization through changes in prey availability.

Variation in potential for isoprene emissions among Neotropical forest sites - Peter Harley; Pérola Vasconcellos; Lee Vierling; Carlos Cleomir de S. Pinheiro; James Greenberg; Alex Guenther; Lee Klinger; Samuel Soares de Almeida; David Neill; Tim Baker; Oliver Phillips; Yadvinder Malhi (Global Change Biology, 2004)
As part of the Large Scale Biosphere–Atmosphere Experiment in Amazônia (LBA), we have developed a bottom‐up approach for estimating canopy‐scale fluxes of isoprene. Estimating isoprene fluxes for a given forest ecosystem requires knowledge of foliar biomass, segregated by species, and the isoprene emission characteristics of the individual tree species comprising the forest. In this study, approximately 38% of 125 tree species examined at six sites in the Brazilian Amazon emitted isoprene. Given logistical difficulties and extremely high species diversity, it was possible to screen only a small percentage of tree species, and we propose a protocol for estimating the emission capacity of unmeasured taxa using a taxonomic approach, in which we assign to an unmeasured genus a value based on the percentage of genera within its plant family which have been shown to emit isoprene. Combining this information with data obtained from 14 tree censuses at four Neotropical forest sites, we have estimated the percentage of isoprene‐emitting biomass at each site. The relative contribution of each genus of tree is estimated as the basal area of all trees of that genus divided by the total basal area of the plot. Using this technique, the percentage of isoprene‐emitting biomass varied from 20% to 42% (mean=31%; SD=8%). Responses of isoprene emission to varying light and temperature, measured on a sun‐adapted leaf of mango ( Mangifera indica L.), suggest that existing algorithms developed for temperate species are adequate for tropical species as well. Incorporating these algorithms, estimates of isoprene‐emitting biomass, isoprene emission capacity, and site foliar biomass into a canopy flux model, canopy‐scale fluxes of isoprene were predicted and compared with the above‐canopy fluxes measured at two sites. Our bottom‐up approach overestimates fluxes by about 50%, but variations in measured fluxes between the two sites are largely explained by observed variation in the amount of isoprene‐emitting biomass.

Maternal Risk Factors for Testicular Cancer: A Population-Based Case–Control Study (UK) - Carol A.C. Coupland; David Forman; Clair E.D. Chilvers; Gwyneth Davey; Malcolm C. Pike; R. Tim D. Oliver (Cancer Causes & Control, 2004)

Differential region-specific regulation of central ?1-adrenoceptor binding following chronic haloperidol and clozapine administration in the rat - Marie Cahir; Tim Mawhinney; David J. King (Psychopharmacology, 2004)

Limited effect of anthropogenic habitat fragmentation on molecular diversity in a rain forest skink, Gnypetoscincus queenslandiae - Joanna Sumner; Tim Jessop; David Paetkau; Craig Moritz (Molecular Ecology, 2004)
To examine the effects of recent habitat fragmentation, we assayed genetic diversity in a rain forest endemic lizard, the prickly forest skink ( Gnypetoscincus queenslandiae ), from seven forest fragments and five sites in continuous forest on the Atherton tableland of northeastern Queensland, Australia. The rain forest in this region was fragmented by logging and clearing for dairy farms in the early 1900s and most forest fragments studied have been isolated for 50–80 years or nine to 12 skink generations. We genotyped 411 individuals at nine microsatellite DNA loci and found fewer alleles per locus in prickly forest skinks from small rain forest fragments and a lower ratio of allele number to allele size range in forest fragments than in continuous forest, indicative of a decrease in effective population size. In contrast, and as expected for populations with small neighbourhood sizes, neither heterozygosity nor variance in allele size differed between fragments and sites in continuous forests. Considering measures of among population differentiation, there was no increase in F ST among fragments and a significant isolation by distance pattern was identified across all 12 sites. However, the relationship between genetic ( F ST ) and geographical distance was significantly stronger for continuous forest sites than for fragments, consistent with disruption of gene flow among the latter. The observed changes in genetic diversity within and among populations are small, but in the direction predicted by the theory of genetic erosion in recently fragmented populations. The results also illustrate the inherent difficulty in detecting genetic consequences of recent habitat fragmentation, even in genetically variable species, and especially when effective population size and dispersal rates are low.

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Evaluation of Hydrologically Relevant PCM Climate Variables and Large-Scale Variability over the Continental U.S. - Chunmei Zhu; David W. Pierce; Tim P. Barnett; Andrew W. Wood; Dennis P. Lettenmaier (Climatic Change, 2004)

The ACPI Project, Element 1: Initializing a Coupled Climate Model from Observed Conditions - David W. Pierce; Tim P. Barnett; Robin Tokmakian; Albert Semtner; Mathew Maltrud; JoAnne Lysne; Anthony Craig (Climatic Change, 2004)

Wall Shear Stress Modulation of ATP/ADP Concentration at the Endothelium - Tim David (Annals of Biomedical Engineering, 2003)

Association of Fusarium Species in the Wheat Stem Rot Complex - Tim Pettitt; Xiangming Xu; David Parry (European Journal of Plant Pathology, 2003)

Preliminary Investigation of Submerged Aquatic Vegetation Mapping using Hyperspectral Remote Sensing - David J. Williams; Nancy B. Rybicki; Alfonso V. Lombana; Tim M. O'Brien; Richard B. Gomez (Environmental Monitoring and Assessment, 2003)

Similar estimates of population genetic composition and sex ratio derived from carcasses and faeces of Eurasian otter Lutra lutra - John F. Dallas; Karen E. Coxon; Tim Sykes; Paul R. F. Chanin; Freda Marshall; David N. Carss; Philip J. Bacon; Stuart B. Piertney; Paul A. Racey (Molecular Ecology, 2003)
Collecting faeces is viewed as a potentially efficient way to sample elusive animals. Nonetheless, any biases in estimates of population composition associated with such sampling remain uncharacterized. The goal of this study was to compare estimates of genetic composition and sex ratio derived from Eurasian otter Lutra lutra spraints (faeces) with estimates derived from carcasses. Twenty per cent of 426 wild‐collected spraints from SW England yielded composite genotypes for 7–9 microsatellites and the SRY gene. The expected number of incorrect spraint genotypes was negligible, given the proportions of allele dropout and false allele detection estimated using paired blood and spraint samples of three captive otters. Fifty‐two different spraint genotypes were detected and compared with genotypes of 70 otter carcasses from the same area. Carcass and spraint genotypes did not differ significantly in mean number of alleles, mean unbiased heterozygosity or sex ratio, although statistical power to detect all but large differences in sex ratio was low. The genetic compositions of carcass and spraint genotypes were very similar according to confidence intervals of θ and two methods for assigning composite genotypes to groups. A distinct group of approximately 11 carcass and spraint genotypes was detected using the latter methods. The results suggest that spraints can yield unbiased estimates of population genetic composition and sex ratio.

Cultural, environmental and historical controls of vegetation patterns and the modern conservation setting on the island of Martha's Vineyard, USA - David R. Foster; Brian Hall; Sylvia Barry; Susan Clayden; Tim Parshall (Journal of Biogeography, 2002)
Aim Long‐term studies of landscape dynamics in relationship to changes in cultural, environmental and disturbance factors have great potential for increasing the understanding of modern ecological conditions and improving the development of conservation plans that incorporate historically important processes. In this study we compiled archaeological, historical, palaeoecological and ecological information on Martha's Vineyard to investigate temporal and spatial variation in landscape pattern and process. Although 2 , this island off the Massachusetts coast embraces remarkable geographical variation and harbours uncommon plant and animal assemblages that make it a national priority for conservation. Location The study embraces the entire island of Martha's Vineyard, which lies c. 8 km south of Cape Cod and the mainland of Massachusetts. The triangular‐shaped island contains three major geomorphological regions: moraine forms a series of irregular and subparallel ridges and hills 40 to over 80 m in elevation that terminate at the western end of the island in high cliffs at Gay Head and Squibnocket; sandy glacial outwash overlying moraine spreads down the northeastern end of the island forming a region of low undulating hills and shallow depressions 15–30 m in elevation, and an extensive outwash plain stretches across the central and eastern part of the island and slopes gently from 30‐m elevation in the north to 100 m of Quaternary and coastal plain sediments. Methods Long‐term records of vegetation, fire, natural disturbance and human activity were compiled over the past 2000 years and across the physiographic variation on the island. Palaeoecological interpretations of vegetation, fire, climate and land‐use history are based on a series of eleven stratigraphies from ponds, lakes and wetlands; archaeological data were compiled from recent surveys; historical data were assembled from census and town records, fire records, aerial photographs and cartographic series; and ecological information was derived from forestry and conservation surveys and field sampling of vegetation, soils and site characteristics. Extensive use was made of geographical information systems and multivariate statistical analyses. Results Spatial patterns in vegetation over the past 2000 years have varied strongly with soils and physiography, which are also associated with major differences in fire and land‐use history. Mesic hardwood forests that seldom burned occupy the western moraine, open oak‐pine and hardwood forests occur on the frequently burned and dissected outwash plain along the south coast, and pine‐oak forests cover the central outwash plain, which extends across much of the island and displays among the highest charcoal values in New England. Although a relatively large Native American population may have been an important source of fire ignitions there is no palynological or archaeological evidence that this culture cleared substantial areas or directly altered the extent of forest cover. Shifts in forest composition and fire were associated with regional climate change during the pre‐European period, whereas pronounced changes in forest cover and the development of extensive open‐land areas of grassland, shrubland and heathland were driven by European land use. The contrasting characteristics, land‐use histories and ownerships of different regions of the island yield contrasting conservation priorities and management directions. The mesic morainal forests have changed modestly in composition during the historical period and can effectively support a distinct woodland flora if adequately protected. The large outwash plain is broken by non‐native plantations but could yield an effective landscape mosaic of oak and pine forests interrupted by extensive scrub oak barrens that could be maintained through prescribed fire or cutting. In contrast, the south shore grasslands and shrublands are the product of intensive agricultural land use. These habitats and their unusual suite of plants and animals require traditional land‐use practices, or their substitutes, in order to reverse the ongoing increase in woody species and to maintain these cultural landscapes. Main Conclusion The biotic, edaphic, disturbance and historical diversity across this relatively small landscape is remarkable and yet poses many challenges to interpretation and conservation. The modern landscape can only be understood through knowledge of its long‐term past and can be best managed in the context of the natural and cultural factors that have shaped it through time.

Effects of Long‐Term Ungulate Exclusion and Recent Alien Species Control on the Preservation and Restoration of a Hawaiian Tropical Dry Forest - Robert J. Cabin; Stephen G. Weller; David H. Lorence; Tim W. Flynn; Ann K. Sakai; Darren Sandquist; Lisa J. Hadway (Conservation Biology, 2000)
Although the destruction of tropical rain forests receives much attention, tropical dry forests are in general far more threatened and endangered. Eliminating grazing ungulates is often considered a key first step toward protecting these ecosystems, but few studies have investigated the long‐term effects of this technique. We examined the effects of ungulate exclusion from a 2.3‐ha native dry‐forest preserve on the island of Hawaii by comparing its present flora to the flora of an adjacent area subjected to continuous grazing since the preserve was fenced over 40 years ago. Relative to this adjacent area, the fenced preserve contained a more diverse flora with substantially greater coverage of native overstory and understory species. Until recently, however, regeneration of native canopy trees within the preserve appears to have been thwarted by a dominant herbaceous cover of alien fountain grass ( Pennisetum setaceum ) and predation by alien rodent species. Our results indicate that although ungulate exclusion may be a necessary and critical first step, it is not sufficient to adequately preserve and maintain Hawaii's remaining tropical dry forest remnants. Our recent efforts to control the dominant alien species within the fenced preserve suggest that this practice may facilitate both the regeneration of native species and the colonization and potential invasion of new alien plants. Comparisons of seedlings of the dominant native canopy tree Diospyros sandwicensis growing in sites both dominated by and free of fountain grass suggested that fountain grass inhibits Diospyros seedling growth and photosynthesis but may increase survival if seedlings are protected from ungulates.

Evidence for short-lived oscillations in the biological records from the sediments of Lago Albano (Central Italy) spanning the period ca. 28 to 17 k yr BP - Piero Guilizzoni; Aldo Marchetto; Andrea Lami; Frank Oldfield; Marina Manca; Claudio A. Belis; Anna M. Nocentini; Patrizia Comoli; Vivienne J. Jones; Steve Juggins; Christina Chondrogianni; Daniel Ariztegui; et al. (Journal of Paleolimnology, 2000)

H-OBIS: A Historical Dimension to the Ocean Biogeographical Information System - David Starkey; Poul Holm; Tim Smith; Robert Francis; Helen Rozwadowski (Oceanography, 2000)

Behavior of a cell line derived from normal human hepatocytes on non-physiological and physiological-type substrates: Evidence for enhancement of secretion of liver-specific proteins by a three-dimensional growth pattern - Matthew Smalley; Kenneth Leiper; David Floyd; Margaret Mobberley; Tim Ryder; Clare Selden; Eve A. Roberts; Humphrey Hodgson (In Vitro Cellular & Developmental Biology - Animal, 1999)

Patterns of courtship behavior and ejaculate characteristics in male red-winged blackbirds - David F. Westneat; Lisa A. McGraw; Jennifer M. Fraterrigo; Tim R. Birkhead; F. Fletcher (Behavioral Ecology and Sociobiology, 1998)

Small faults and kink bands in the Nankai accretionary complex: Textural observations from Site 808 of ODP Leg 131 - Jonathan C. Lewis; Tim Byrne; David J. Prior (Island Arc, 1997)
We present backscattered scanning electron microscope and petrographic microscope observations of deformed sediments from Ocean Drilling Program (ODP) Site 808 in order to better understand the dewatering and deformation history of the Nankai accretionary complex. This synthesis of deformation textures has three implications. First, the early structures that dominate the Nankai prism, small faults and kink bands, have very different electron microscope versus optical microscopic expressions. This observation is important to investigations of fine‐grained sediment in both stable and active tectonic settings, in part, because these materials have often been studied almost exclusively by electron microscope methods. In sediments of this type, investigators often forego petrographic analysis because of the relative opacity of samples at normal (i.e. 30 pm) thin section thicknesses. Second, the textural observations we have compiled suggest that these deformation structures acted as ‘single‐event’ pathways that contributed to diffusive dewatering of the prism. Third, our observations serve as a reference frame for the early tectonic structures that are important to the dewatering history of a ‘sandy’ accretionary prism.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)